Articles Comprising Sorbents, Polymer Composites, and Halide Precursor Compositions, Methods for Adsorbing Mercury and Sulfur Oxides on Articles, and Methods for Making Articles Comprising Sorbent Articles

A layered pollution control system with a sorbent polymer composite and halogen reservoir addresses the inefficiencies of existing systems by providing durable and efficient removal of SOx, mercury vapor, and PM2.5 from flue gases, ensuring prolonged operation without secondary pollutant generation.

JP7607765B2Active Publication Date: 2024-12-27WL GORE & ASSOC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023528285
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-12
Filing Date
2021-11-12
Publication Date
2024-12-27
Estimated Expiration
2041-11-12

AI Technical Summary

Technical Problem

Existing pollution control systems for industrial flue gases, such as those from coal-fired power plants, struggle to efficiently and durably remove sulfur oxides (SOx), mercury vapor, and particulate matter (PM2.5) without generating secondary pollutants, and halogen sources in these systems often leach or degrade quickly.

Method used

A pollution control system featuring a layered structure with a sorbent polymer composite (SPC) and a halogen reservoir that includes a permeation control material, allowing for controlled release of halogen sources over an extended period, thereby enhancing the durability and efficiency of pollutant removal.

Benefits of technology

The system effectively removes SOx, mercury vapor, and PM2.5 over an extended period without generating secondary pollutants, maintaining high removal efficiency and durability by using a halogen reservoir that delays halogen release, thus extending the system's operational lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607765000009
    Figure 0007607765000009
  • Figure 0007607765000010
    Figure 0007607765000010
  • Figure 0007607765000011
    Figure 0007607765000011
Patent Text Reader

Abstract

A durable pollution control system, article, and method for removing a variety of flue gas pollutants. The pollution control system is capable of providing a required amount of halogen source over an extended period of time. The halogen source is incorporated into a sorbent polymer composite substrate. The sorbent polymer composite substrate is configured to prevent the halogen from leaching in solutions formed during the pollutant gas treatment process.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 113,022, filed November 12, 2020, entitled “LAYERED ARTICLES COMPRISING A HALOGEN RESERVOIR, SYSTEMS AND METHODS INCLUDING THE SAME,” the entirety of which is incorporated herein by reference.

[0002] FIELD OF THE DISCLOSURE This disclosure relates to the field of pollution control systems and methods for removing compounds and particulate matter from gas streams. [Background technology]

[0003] Coal-fired power plants, municipal waste incinerators, and oil refineries generate large amounts of flue gases. The flue gases contain a wide variety of environmental pollutants, such as sulfur oxides (SO2 and SO3), nitrogen oxides (NO, NO2), mercury (Hg) vapor, and particulate matter (PM). In the United States, burning coal alone produces approximately 27 million tons of SO2 and 45 tons of Hg annually. Thus, there is a need for improved control systems and methods for removing sulfur oxides, mercury vapor, and particulate matter from industrial flue gases, such as coal-fired power plant flue gases. Summary of the Invention [Means for solving the problem]

[0004] In some embodiments, an improved and durable pollution control system is provided that can simultaneously remove a variety of flue gas pollutants. These pollutants include, but are not limited to, SO x, Hg vapor, and PM2.5 (particulate matter with a diameter of 2.5 micrometers or less). Some embodiments may include a simple pollution control system that does not generate secondary pollutants. In some embodiments, the pollution control system may provide the required amount of halogen source for an extended period of time. Specifically, the flue gas treatment device may include a more durable and longer lasting halogen source in combination with a sorbent polymer composite substrate. In some embodiments, the sorbent polymer composite substrate is not leached with solutions generated during the treatment process. Some embodiments of the present disclosure relate to articles having a layered structure that may include a halogen source and SPC. In some embodiments, the articles described herein allow for delayed release of at least one halogen source from a halogen reservoir. The halogen reservoir may form part of the articles described herein.

[0005] In some embodiments, the article comprises a flue gas treatment device. In some embodiments, the article is a flue gas treatment device. In some embodiments, the article is part of a flue gas treatment device.

[0006] In some embodiments, the article includes a first sorbent polymer composite (SPC) layer, a second SPC layer, and a halogen reservoir, the halogen reservoir being disposed between the first SPC layer and the second SPC layer.

[0007] In some embodiments, the article comprises, or further comprises, at least one permeation control material.

[0008] In some embodiments of the article, the at least one permeation control material is in the form of at least one permeation control layer disposed between the first SPC layer and the halogen reservoir, between the second SPC layer and the halogen reservoir, or both, i.e., in some embodiments of the article, the at least one permeation control layer is in the form of at least one permeation control layer disposed between the first SPC layer and the halogen reservoir and also between the second SPC layer and the halogen reservoir.

[0009] In some embodiments of the article, the at least one permeation control layer comprises a first layer of the at least one permeation control material, the first layer being disposed between the first SPC layer and the halogen reservoir, and a second layer of the at least one permeation control material, the second layer being disposed between the second SPC layer and the halogen reservoir.

[0010] In some embodiments of the article, the halogen reservoir comprises at least one halogen source.

[0011] In some embodiments of the article, the at least one halogen source comprises at least one halide ion or elemental halogen.

[0012] In some embodiments of the article, the halogen reservoir comprises 0.1 wt % to 50 wt % of at least one halogen source, based on the total weight of the halogen reservoir.

[0013] In some embodiments of the article, the halogen reservoir comprises SPC.

[0014] In some embodiments of the article, the halogen reservoir comprises a third SPC layer.

[0015] In some embodiments of the article, at least one of the first SPC layer, the second SPC layer, or the third SPC layer comprises at least one halogen source.

[0016] In some embodiments of the article, the first SPC layer, the second SPC layer, and the third SPC layer comprise at least one halogen source.

[0017] In some embodiments of the article, the halogen reservoir comprises at least one permeation control material.

[0018] In some embodiments of the article, the halogen reservoir comprises 5 wt% to 95 wt% of at least one permeation control material, based on the total weight of the halogen reservoir, and 5 wt% to 50 wt% of at least one halogen source, based on the total weight of the halogen reservoir.

[0019] In some embodiments, the article comprises a first permeation control material and a second permeation control material, the second permeation control material being in the form of at least two layers of the second permeation control material.

[0020] In some embodiments of the article, the at least one permeation control material comprises a first permeation control material and a second permeation control material, the second permeation control material being in the form of at least one layer of the second permeation control material, the at least one layer of the second permeation control material being disposed between the first SPC layer and the halogen reservoir.

[0021] In some embodiments of the article, the at least one permeation control material comprises a first permeation control material and a second permeation control material, the second permeation control material being in the form of at least one layer of the second permeation control material, the at least one layer of the second permeation control material being disposed between the second SPC layer and the halogen reservoir.

[0022] In some embodiments of the article, the at least one permeation control material comprises a first permeation control material and a second permeation control material, the second permeation control material being in the form of at least one layer of the second permeation control material, the at least one layer of the second permeation control material being disposed between the first SPC layer and the halogen reservoir, and also between the second SPC layer and the halogen reservoir.

[0023] In some embodiments of the article, the at least one layer of the second permeation control material includes a first layer of the second permeation control material, where the first layer of the second permeation control material is disposed between the first SPC layer and the halogen reservoir, and a second layer of the second permeation control material, where the second layer of the second permeation control material is disposed between the second SPC layer and the halogen reservoir.

[0024] In some embodiments of the article, the halogen reservoir further comprises carbon particles.

[0025] In some embodiments of the article, the carbon particles are embedded within the at least one permeation control material.

[0026] Some such embodiments involve flowing a flue gas stream over at least one surface of the article for a period of at least 90 days, the gas stream having a temperature of at least 20° C. and a relative humidity of at least 95%, and the gas stream containing at least one SO 2 species at a concentration of at least 1 ppm. x and at least 1 μg / m based on the total volume of said flue gas stream. 3 and mercury vapor at a concentration of

[0027] In some embodiments, the article has a release rate of total halogens from the article that does not exceed 0.5% of the total halogens in the article per day when a flue gas stream is caused to flow over at least one surface of the article for a period of at least 90 days, the flue gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%, and the flue gas stream has a concentration of at least one SO 2 species at least equal to 20 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of

[0028] In some embodiments, the article has a release rate of total halogens from the article that does not exceed 2% of the total halogens in the article per day when a flue gas stream is caused to flow over at least one surface of the article for a period of at least 90 days, the flue gas stream has a temperature of at least 20° C. and a relative humidity of at least 95%, and the flue gas stream contains at least one SO 2 species at a concentration of at least 1 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of

[0029] In some embodiments, the article comprises a filter laminate, a layered filter material, an SPC laminate, or a layered SPC material.

[0030] In some embodiments, a method of forming an article includes forming the article by obtaining a first sorbent polymer composite (SPC) layer, obtaining a second SPC layer, obtaining a halogen reservoir, disposing the halogen reservoir between the first SPC layer and the second SPC layer to produce a layered structure, and adhering the layered structure together.

[0031] In some embodiments of the method, disposing the halogen reservoir between the first SPC layer and the second SPC layer includes disposing the at least one permeation control layer between the first SPC layer and the halogen reservoir, disposing at least one permeation control layer between the second SPC layer and the halogen reservoir, or both, such that the formed article includes at least one permeation control layer.

[0032] In some embodiments of the method, disposing the halogen reservoir between the first SPC layer and the second SPC layer includes disposing a first layer of at least one permeation control material between the first SPC layer and the halogen reservoir, and disposing a second layer of at least one permeation control material between the second SPC layer and the halogen reservoir.

[0033] In some embodiments, the method includes or further includes combining at least one halogen source and at least one permeation control material to form the halogen reservoir, the halogen reservoir comprising the at least one halogen source and the at least one permeation control material.

[0034] In some embodiments of the method, combining the at least one halogen source with the at least one permeation control material comprises heating the at least one permeation control material to a temperature sufficient to melt the at least one permeation control material, and mixing the at least one molten permeation control material with the at least one halogen source.

[0035] In some embodiments of the method, the temperature sufficient to melt the at least one permeation control material is between 130°C and 180°C.

[0036] In some embodiments of the method, combining the at least one halogen source with the at least one permeation control material comprises dissolving the at least one permeation control material in a solvent to form a mixture, adding at least one halogen source to the mixture of the solvent and the at least one permeation control material, and evaporating the solvent.

[0037] In some embodiments, the method includes or further includes adding particles to the mixture of the at least one halogen source, a solvent, and the at least one permeation control material.

[0038] In some embodiments of the method, the particles are carbon particles.

[0039] In some embodiments of the method, combining the at least one halogen source with the at least one permeation control material comprises forming a chemical complex having the at least one halogen source and the at least one permeation control material.

[0040] In some embodiments of the method, the at least one halogen source is in solution.

[0041] In some embodiments of the method, the at least one halogen source is in the gas phase.

[0042] In some embodiments of the method, the at least one halogen source is a salt.

[0043] In some embodiments of the method, the at least one halogen source is in solution, gas phase, a salt, or any combination thereof.

[0044] In some embodiments, the method includes, or further includes, flowing a flue gas stream over at least one surface of the article for a period of at least 90 days, wherein the flue gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%, and wherein the flue gas stream contains at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m based on the total volume of said flue gas stream. 3 and mercury vapor at a concentration of 0.5% by weight of the total halogens in said article per day during flow of said flue gas stream.

[0045] In some embodiments, the method further comprises flowing a flue gas stream over at least one surface of the article for a period of at least 90 days, wherein the flue gas stream has a temperature of at least 20° C. and a relative humidity of at least 95%, and wherein the flue gas stream contains at least one SO 2 species at a concentration of at least 1 ppm. x and at least 1 μg / m based on the total volume of said flue gas stream. 3 and mercury vapor at a concentration of 100 to 200 nm, and wherein during flow of said flue gas stream the release rate of the total halogens in said article does not exceed 2% of the total halogens in said article per day. [Brief description of the drawings]

[0046] Certain embodiments of the present disclosure will now be described, by way of example, with reference to the accompanying drawings. With specific reference now to the drawings in detail, it is emphasized that the illustrated embodiments are by way of example only and are for the purpose of illustratively discussing embodiments of the present disclosure. In this regard, the description taken together with the drawings will make apparent to those skilled in the art how embodiments of the present disclosure may be practiced.

[0047] [Figure 1] FIG. 1 illustrates a non-limiting embodiment of the article described herein.

[0048] [Figure 2A]FIG. 2A illustrates a non-limiting embodiment of an article described herein having a sorbent-polymer composite as a halogen reservoir for at least one halogen source.

[0049] [Figure 2B] FIG. 2B illustrates a further non-limiting embodiment of the article of FIG. 2A having, for example, two permeation control layers.

[0050] [Figure 3A] FIG. 3A illustrates a non-limiting embodiment of an article described herein that includes a halogen reservoir, the halogen reservoir including at least one permeation control material and at least one halogen source.

[0051] [Figure 3B] FIG. 3 illustrates a further non-limiting embodiment of the article of FIG. 3A having multiple permeation control layers.

[0052] [Figure 3C] FIG. 3C illustrates a further non-limiting embodiment of FIG. 3A, where the halogen reservoir comprises particles.

[0053] [Figure 3D] FIG. 3D illustrates a further non-limiting embodiment of FIG. 3C in which the halogen reservoir contains particles and further comprises two permeation control layers.

[0054] [Figure 4] FIG. 4 illustrates a non-limiting embodiment of a pollution control system having any of the articles described herein.

[0055] [Diagram 5] FIG. 5 is a diagram illustrating a non-limiting embodiment of a flue gas flowing over a non-limiting embodiment of an article described herein.

[0056] [Figure 6A]FIG. 6A is a graph showing relative iodine content over time based on the non-limiting embodiments shown in Example Articles 1C and 1D.

[0057] [Figure 6B] FIG. 6B is a graph showing relative iodine content over time based on the non-limiting embodiments shown in Example Articles 1A and 1B.

[0058] [Figure 7A] FIG. 7A is a graph showing iodine content in wt % versus time based on the non-limiting embodiment shown in Example Articles 2A and 2B.

[0059] [Figure 7B] FIG. 7B is a graph showing iodine content in wt % versus time based on the non-limiting embodiments shown in Example Articles 2C and 2D.

[0060] [Figure 8A] FIG. 8A is a graph showing relative iodine content over time based on the non-limiting embodiment shown in Example Articles 3A and 3B.

[0061] [Figure 8B] FIG. 8B is a graph showing relative iodine content over time based on the non-limiting embodiments shown in Example Articles 3C-3G.

[0062] [Figure 8C] FIG. 8C is an EDX mapping showing the halogen content of a cross section of Example Article 3B.

[0063] [Figure 8D] FIG. 8D is an EDX mapping showing the sulfur content of a cross section of example article 3B.

[0064] [Figure 8E] FIG. 8E is an EDX mapping showing the halogen content of a cross section of example article 3G.

[0065] [Figure 9] FIG. 9 is a graph showing relative iodine content over time based on the non-limiting embodiments shown in Example Articles 4A and 4B.

[0066] [Figure 10] FIG. 10 is a graph showing relative iodine content versus time based on Comparative Examples 5A and 5B.

[0067] [Figure 11] FIG. 11 is a graph showing relative iodine content over time based on Comparative Examples 5A and 5B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0068] Detailed Description Among the disclosed benefits and improvements, other objects and advantages of the present disclosure will become apparent from the following description taken in conjunction with the accompanying drawings. Detailed embodiments of the present disclosure are disclosed herein, but it should be understood that the disclosed embodiments are merely examples of the disclosed subject matter that may be embodied in various forms. In addition, each of the examples provided in connection with the various embodiments of the present disclosure are illustrative and not limiting.

[0069] Throughout the specification and claims, the following terms shall have the meanings explicitly associated therewith, unless the context clearly dictates otherwise. As used herein, the phrases "in one embodiment," "in an embodiment," and "in some embodiments" do not necessarily refer to the same embodiment, although they may. Additionally, as used herein, the phrases "in another embodiment" and "in some other embodiments" do not necessarily refer to different embodiments, although they may. It is intended that all embodiments of the present disclosure may be combined without departing from the scope or spirit of the present disclosure.

[0070] The term "between" as used herein does not necessarily mean that something is located immediately adjacent to another element. In general, the term refers to something being sandwiched between two or more other things. At the same time, the term "between" can also refer to something that is directly adjacent to two opposing things. Thus, in any one or more of the embodiments disclosed herein, a specific structural component that is located between two other structural elements is: It may be disposed directly between both of the two other structural elements, such that the particular structural component is in direct contact with both of the two other structural elements, or It may be disposed directly adjacent to only one of the two other structural elements, such that a particular structural component is in direct contact with only one of the two other structural elements, or It may be indirectly adjacent to only one of the two other structural elements, so that the particular structural component is not in direct contact with only one of the two other structural elements, and there is another element that juxtaposes the particular structural component with the one of the two other structural elements, or be indirectly adjacent to and between both of the two other structural elements, such that the particular structural component is not in direct contact with both of the two other structural elements and other features may be disposed therebetween; or Any combination of these may be arranged.

[0071] As used herein, the term "based on" is not exclusive and allows for based on additional unrecited factors, unless the context clearly dictates otherwise. Additionally, throughout the specification, the meanings of "a," "an," and "the" include plural references. The meaning of "in" includes "in" and "on."

[0072] All prior patents and publications cited herein are incorporated by reference in their entirety.

[0073] SPC has been found to be particularly effective in removing undesirable components from flue gas streams. One example of such an undesirable component is at least one SO x Chemical compounds and mercury vapor.

[0074] The use of at least one halogen source can increase the removal efficiency of SPC. However, in some cases, the at least one halogen source may not be durable enough to allow the SPC (and the system containing it, such as a fixed bed absorption system) to continue to operate for many years. In some cases, this occurs because the at least one halogen source may leach out of the sorbent when added.

[0075] As used herein, the term "removal efficiency" refers to the performance of a pollution control system as the ratio of the amount of a regulated pollutant removed from an air stream (e.g., flue gas) to the total amount of regulated pollutant entering the pollution control system. Thus, "removal efficiency" for a "particular pollutant" refers to the percentage of that pollutant removed by the pollution control system. For example, removal efficiency for NOX can be measured as the percentage reduction in NOX concentration achieved by the pollution control system. This percentage reduction shall be calculated by subtracting the outlet concentration from the inlet concentration, dividing the difference by the inlet concentration, and then multiplying the result by 100.

[0076] Some embodiments of the present disclosure provide an exemplary solution in which a halogen reservoir (e.g., in the form of a layer) allows at least one halogen source to be released over time. The halogen reservoir allows the SPC (and systems including same, e.g., fixed bed absorption systems) to operate (e.g., be in service) for a longer period of time compared to an SPC that does not include a halogen reservoir.

[0077] As used herein, "sorbent" means a substance that has the property of collecting molecules of another substance by at least one of absorption, adsorption, or a combination thereof.

[0078] In some embodiments, the SPC comprises a sorbent. In some embodiments, the sorbent of the SPC comprises activated carbon. In some embodiments, the sorbent comprises activated carbon derived from coal, lignite, wood, coconut shell, another carbonaceous material, or any combination thereof. In some embodiments, the sorbent can comprise silica gel, zeolite, or any combination thereof.

[0079] As used herein, the term "composite" refers to a material that includes two or more component materials having different physical or chemical properties that, when combined, result in a material having characteristics that differ from those of the individual components.

[0080] As used herein, a "sorbent polymer composite (SPC)" is a composite comprising a sorbent and a polymer. The sorbent polymer composite material further comprises a halogen source. In some embodiments, the halogen source may be incorporated into the sorbent polymer composite material by any suitable technique, including, but not limited to, imbibing, impregnating, adsorbing, mixing, sprinkling, spraying, dipping, painting, coating, ion exchange, or otherwise applying the halogen source to the sorbent polymer composite. In some embodiments, the halogen source may be disposed within the sorbent polymer composite material, for example, within any pores of the sorbent polymer composite material. In some embodiments, the halogen source may be provided in a solution. The solution may be contacted in situ with the sorbent polymer composite material under system operating conditions. The halogen source of the sorbent polymer composite may be a halogen salt, an elemental halogen, or any combination thereof. In some embodiments, the halogen source is selected from at least one of sodium chloride, potassium chloride, sodium bromide, potassium bromide, sodium iodide, potassium iodide, tetramethylammonium iodide, tetrabutylammonium iodide, tetraethylammonium iodide, tetrapropylammonium iodide, tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, elemental iodine (I2), elemental chlorine (Cl2), elemental bromine (Br2), or any combination thereof.

[0081] Additional forms of the sorbent polymer complexes described herein, and additional examples of the halogen sources described herein, are described in U.S. Patent No. 9,827,551 (1368) to Hardwick et al., and U.S. Patent No. 7,442,352 to Lu et al., each of which is incorporated herein by reference in its entirety.

[0082] As used herein, the term "reservoir" refers to a reservoir that contains at least one material. The reservoir is configured to release at least one material over a period of time. In some non-limiting embodiments, the reservoir can include at least one permeation control material.

[0083] The term "halogen reservoir" as used herein means a reservoir containing at least one halogen source, wherein the at least one halogen source is configured to be released from storage over a period of time. As used herein, "halogen reservoir" and "reservoir" can be used interchangeably without changing the meaning of each term.

[0084] As used herein, "embedded" means that a first material is distributed throughout a second material.

[0085] As used herein, the term "permeation control material" refers to a material that is configured to release one or more substances from a reservoir at a slower rate than if the substances were released in the absence of a permeation control layer.

[0086] As used herein, the term "halogen source" means any compound that contains at least one halide ion or elemental halogen.

[0087] The halogen source of the flue gas treatment device is selected from tetrabutylammonium iodide, tetrabutylammonium triiodide, tetrabutylammonium tribromide, or tetrabutylammonium bromide. In another embodiment, the halogen source is a compound having the formula N(R1R2R3R4)X, where N is nitrogen and X=I. - ,Br - ,I3 - ,BrI2 - ,Br2I - ,Br3- and R1, R2, R3, and R4 are selected from the group consisting of hydrocarbons having from about 1 to about 18 carbon atoms, which may be simple alkyls, including, for example, linear or branched alkyls. The halogen source may include a trihalide, which is formed from its halide precursor by acid treatment in the presence of an oxidizing agent. In a further embodiment, the halogen source is a trihalide, which is formed from its halide precursor by acid treatment in the presence of an oxidizing agent, which is selected from the group consisting of hydrogen peroxide, alkali metal persulfates, alkali metal monopersulfates, potassium iodate, potassium monopersulfate, oxygen, iron(III) salts, iron(III) nitrate, iron(III) sulfate, iron(III) oxide, and combinations thereof.

[0088] As used herein, the "total halogen release rate" is the release rate of the at least one halogen source from the article into the external environment in which the article resides. In some non-limiting embodiments, the external environment may be a combustion exhaust gas stream. In some embodiments, the at least one halogen source is released into the external environment exclusively from the SPC. In these embodiments, the "total halogen release rate" is the release rate from the SPC into the external environment. In some embodiments, the at least one halogen source is released into the external environment exclusively from the halogen reservoir. In these embodiments, the "total halogen release rate" is the release rate from the halogen reservoir into the external environment. In some embodiments, the at least one halogen source is released into the external environment from a combination of the SPC and the halogen reservoir. In these embodiments, the "total halogen release rate" is a composite release rate, taking into account the release of the at least one halogen source from both the SPC and the halogen reservoir. In some embodiments, the article comprises multiple halogen sources. In these embodiments, the "total halogen release rate" is a composite release rate that takes into account the release of all of the multiple halogen sources in the article.

[0089] Determining the release rate is discussed further below.

[0090] As used herein, the term "carbon particles" means any particles that contain carbon.

[0091] As used herein, "porous carbon particles" refers to carbon particles that have pores and does not include carbon particles that do not have pores, i.e., porous carbon particles exclude "non-porous" carbon particles.

[0092] The term "combustion exhaust gas stream" as used herein means a gaseous mixture comprising at least one by-product of a combustion process (e.g., a coal combustion process). In some embodiments, the flue gas stream may consist entirely of by-products of the combustion process. In some embodiments, the flue gas stream may include at least one gas at an elevated concentration relative to the concentration resulting from the combustion process. For example, in one non-limiting example, the flue gas stream may be subjected to a "scrubbing process." During the scrubbing process, water vapor may be added to the flue gas stream. Thus, in some such embodiments, the flue gas stream may include an elevated concentration of water vapor relative to the initial water vapor concentration resulting from the combustion. Similarly, in some embodiments, the flue gas stream may include at least one gas at a reduced concentration relative to the initial concentration of the at least one gas output from the combustion process. This may occur, for example, by removing at least a portion of the at least one gas after combustion. In some embodiments, the flue gas stream may be in the form of a gaseous mixture that is a combination of by-products of multiple combustion processes.

[0093] As used herein, "SO x The term "sulfur compound" means any oxide of sulfur. x The compound may specifically refer to gaseous sulfur oxides, which are well-known environmental pollutants. x Non-limiting examples of compounds include sulfur dioxide (SO2) and sulfur trioxide (SO3). SO xAdditional non-limiting examples of compounds include sulfur monoxide (SO), disulfur monoxide (SO), and disulfur dioxide (SO).

[0094] As used herein, the term "mercury vapor" refers to gaseous compounds that contain mercury. Non-limiting examples of mercury vapor include elemental mercury vapor and oxidized mercury vapor.

[0095] As used herein, the term "oxidized mercury vapor" is defined as a vapor phase mercury compound that contains mercury in the positive valence state. Non-limiting examples of oxidized mercury vapor include mercurous halide and mercuric halide.

[0096] Some embodiments of the present disclosure relate to an article comprising a first SPC layer, a second SPC layer, and a halogen reservoir. In some embodiments, the halogen reservoir comprises at least one halogen source. In some embodiments, the halogen reservoir is disposed between the first SPC layer and the second SPC layer.

[0097] In some embodiments, the thickness of at least one of the first SPC layer or the second SPC layer can be measured using cross-sectional scanning electron microscopy. In some embodiments, the thickness of at least one of the first SPC layer or the second SPC layer is 0.2 mm to 2 mm, 0.4 mm to 2 mm, 0.8 mm to 2 mm, 1.2 mm to 2 mm, or 1.6 mm to 2 mm.

[0098] In some embodiments, the thickness of at least one of the first SPC layer or the second SPC layer is 0.2 mm to 1.6 mm, 0.2 mm to 1.2 mm, 0.2 mm to 0.8 mm, or 0.2 mm to 0.4 mm.

[0099] In some embodiments, at least one of the first SPC layer or the second SPC layer has a thickness of 0.4 mm to 1.6 mm, or 0.8 mm to 1.2 mm.

[0100] In some embodiments, the SPC may comprise one or more homopolymers, copolymers, or terpolymers containing at least one fluoromonomer with or without additional non-fluorinated monomers.

[0101] In some embodiments, the article comprises a first SPC. In some embodiments, the article comprises a first sorbent and a first polymeric material. In some embodiments, the article comprises a second SPC. In some embodiments, the article comprises a second sorbent and a second polymeric material. In some embodiments, the first sorbent and the second sorbent comprise the same material. In some embodiments, the first sorbent and the second sorbent comprise different materials. In some embodiments, the first polymeric material and the second polymeric material comprise the same material. In some embodiments, the first polymeric material and the second polymeric material comprise different materials.

[0102] In some embodiments, at least one of the first sorbent or the second sorbent comprises activated carbon, silica gel, zeolite, or a combination thereof.

[0103] In some embodiments, the polymeric material of the SPC can include at least one of polyfluoroethylene propylene (PFEP), polyperfluoroacrylate (PPFA), polyvinylidene fluoride (PVDF), terpolymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride (THV), polychlorofluoroethylene (PCFE), poly(ethylene-co-tetrafluoroethylene) (ETFE), ultra-high molecular weight polyethylene (UHMWPE), polyparaxylylene (PPX), polylactic acid (PLLA), polyethylene (PE), expanded polyethylene (ePE), polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (ePTFE), or any combination thereof.

[0104] In some embodiments, the polymeric material of the SPC can include polyvinylidene fluoride (PVDF). In some embodiments, the PVDF can be a PVDF homopolymer. In some embodiments, the PVDF can be a PVDF copolymer. In some embodiments, the PVDF copolymer is a copolymer of PVDF and hexafluoropropylene (HFP). Non-limiting commercial examples of PVDF homopolymers or copolymers suitable for some embodiments of the present disclosure include, but are not limited to, Kynar Flex® and Kynar Superflex®, each commercially available from Arkema.

[0105] In some embodiments, the polymeric material of the SPC can include polytetrafluoroethylene (PTFE). In some embodiments, the polymer is expanded polytetrafluoroethylene (ePTFE). In some embodiments, the structure of the polymer can become porous when stretched, such that voids can form between the fibrils and nodes of the polymer.

[0106] In some embodiments, the surface energy of the polymers of the SPC is less than 31 dynes per cm, less than 30 dynes per cm, less than 25 dynes per cm, less than 20 dynes per cm, or less than 15 dynes per cm.

[0107] In some embodiments, the surface energy of the polymers of the SPC is between 15 dynes per cm and 31 dynes per cm, between 20 dynes per cm and 31 dynes per cm, between 25 dynes per cm and 31 dynes per cm, or between 30 dynes per cm and 31 dynes per cm.

[0108] In some embodiments, the surface energy of the polymers of the SPC is between 15 dynes per cm and 30 dynes per cm, between 15 dynes per cm and 25 dynes per cm, or between 15 dynes per cm and 20 dynes per cm.

[0109] In some embodiments, the surface energy of the polymers in the SPC is between 20 dynes per cm and 25 dynes per cm.

[0110] In some embodiments, the sorbent material of the SPC comprises activated carbon. In some embodiments, the activated carbon material is derived from one or more of coal, lignite, wood, coconut shell, or another carbonaceous material. In some embodiments, the sorbent material can comprise silica gel or zeolite.

[0111] In some embodiments, the surface area of ​​the SPC sorbent is greater than 400 m 2 / g over 600m 2 / g over 800m 2 / g over 1000m 2 / g, 1200m 2 / g, 1400m 2 / g, 1600m 2 / g, 1800m 2 / g, or 2000m 2 / g.

[0112] In some embodiments, the surface area of ​​the SPC sorbent is greater than 400 m 2 / g~2000m 2 / g, 600m 2 / g~2000m 2 / g, 800m 2 / g~2000m 2 / g, 1000m 2 / g~2000m 2 / g, 1200m 2 / g~2000m 2 / g, 1400m 2 / g~2000m 2 / g, 1600m 2 / g~2000m 2 / g, or 1800m 2 / g~2000m 2 / g.

[0113] In some embodiments, the surface area of ​​the SPC sorbent is greater than 400 m 2 / g~1800m2 / g, 400m 2 / g~1600m 2 / g, 400m 2 / g~1400m 2 / g, 400m 2 / g~1200m 2 / g, 400m 2 / g~1000m 2 / g, 400m 2 / g~800m 2 / g, or 400m 2 / g~600m 2 / g.

[0114] In some embodiments, the surface area of ​​the SPC sorbent is greater than or equal to 600 m 2 / g~1800m 2 / g, 800m 2 / g~1600m 2 / g, or 1000m 2 / g~1400m 2 / g.

[0115] In some embodiments, the first SPC layer and the second SPC layer have the same composition. In some embodiments, the first SPC layer and the second SPC layer have different compositions.

[0116] In some embodiments, the at least one permeation control material has a thickness sufficient to provide a release rate constant of total halogen from the article that does not exceed a specified amount of total halogen per day under conditions in which a combustion exhaust gas stream is flowed over at least one surface of the article for a period of at least 90 days.

[0117] In some embodiments, the combustion exhaust gas stream is flowed over at least one surface of the article for a period of at least 100 days, at least 200 days, at least 300 days, at least 400 days, at least 500 days, at least 600 days, at least 700 days, at least 800 days, at least 900 days, at least 1,000 days, at least 2,000 days, at least 3,000 days, at least 4,000 days, or at least 5,000 days.

[0118] In some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of from 100 days to 10,000 days, for a period of from 500 days to 10,000 days, for a period of from 1,000 days to 10,000 days, or for a period of from 5,000 days to 10,000 days.

[0119] In some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of from 100 days to 5,000 days, for a period of from 100 days to 1,000 days, or for a period of from 100 days to 500 days.

[0120] In some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of from 500 days to 10,000 days, or from 1,000 days to 5,000 days.

[0121] Non-limiting numerical examples of "sufficient thickness of at least one permeation control material" are described herein. In some non-limiting embodiments in which the at least one permeation control material forms part of the halogen reservoir, the sufficient thickness of the at least one permeation control material may be considered to be equivalent to the thickness of the halogen reservoir.

[0122] In some non-limiting embodiments in which the at least one permeation control material is in the form of at least one permeation control layer, a sufficient thickness of the at least one permeation control material may be considered to be equivalent to the thickness of a single permeation control layer (in embodiments in which only one permeation control layer is present) or the sum of the thicknesses of multiple permeation control layers (in embodiments in which multiple outer adhesive layers are present).

[0123] In some embodiments, the at least one permeation control material has a thickness sufficient to provide a release rate of total halogens from the article that does not exceed 0.5% of the total halogens per day when a flue gas stream is flowed over at least one surface of the article for a period of at least 90 days, the flue gas stream having a temperature of at least 50° C. and a relative humidity of at least 95%, and the flue gas stream has a concentration of at least one SO 2 species at least equal to 20 ppm. x compounds and at least 1 μg / m of the flue gas stream 3 and mercury vapor at a concentration of

[0124] In some embodiments, the at least one permeation control material has a thickness sufficient to provide a release rate of total halogens from the article that does not exceed 2% of the total halogens per day when a flue gas stream is flowed over at least one surface of the article for a period of at least 90 days, the flue gas stream having a temperature of at least 20° C. and a relative humidity of at least 95%, and the flue gas stream having a concentration of at least one SO 2 species at least equal to 1 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of

[0125] In some embodiments, the release rate (%) refers to the relative amount of halogen over time, not to the weight of the SPC. In some embodiments, as discussed further herein, the decrease in iodine content (or release rate) is exponential (i.e., the decrease can be described as an exponential decay), as shown, for example, in Figures 6A and 6B. Therefore, a constant "k" can be used to describe this behavior. "k" can be referred to as the "release rate constant", "decay constant", or "exponential decay constant".

[0126] In some embodiments, the temperature of the flue gas stream is greater than 20°C, greater than 30°C, greater than 40°C, greater than 50°C, greater than 60°C, greater than 60°C, greater than 70°C, greater than 75°C, greater than 80°C, greater than 85°C, or greater than 90°C.

[0127] In some embodiments, the temperature of the flue gas stream is less than 20°C, less than 30°C, less than 40°C, less than 50°C, less than 60°C, less than 70°C, less than 75°C, less than 80°C, 85°C, or less than 90°C.

[0128] In some embodiments, the temperature of the flue gas stream is between 20°C and 80°C, between 30°C and 80°C, between 40°C and 80°C, between 50°C and 80°C, between 60°C and 80°C, or between 70°C and 80°C.

[0129] In some embodiments, the temperature of the flue gas stream is between 20°C and 70°C, between 20°C and 60°C, between 20°C and 50°C, between 20°C and 40°C, or between 20°C and 30°C.

[0130] In some embodiments, the temperature of the flue gas stream is between 30°C and 70°C, or between 40°C and 60°C.

[0131] In some embodiments, the temperature of the flue gas stream is between 50°C and 70°C, between 60°C and 70°C, between 55°C and 70°C, or between 55°C and 60°C.

[0132] In some embodiments, the temperature of the flue gas stream is between 65°C and 70°C, between 70°C and 75°C, between 75°C and 80°C, between 80°C and 85°C, or between 85°C and 90°C.

[0133] In some embodiments, the temperature of the flue gas stream is between 65°C and 90°C, between 70°C and 90°C, between 75°C and 90°C, between 80°C and 90°C, or between 85°C and 90°C.

[0134] In some embodiments, the temperature of the flue gas stream is between 65° C. and 75° C., between 65° C. and 80° C., between 65° C. and 85° C., or between 65° C. and 90° C. The temperature of the flue gas stream can be measured using a thermometer known to one of skill in the art.

[0135] In some embodiments, the relative humidity of the flue gas stream is at least 95%, at least 96%, at least 97%, at least 98%, at least 99%, or 100%.

[0136] In some embodiments, the relative humidity of the flue gas stream is between 95% and 100%, between 96% and 100%, between 97% and 100%, between 98% and 100%, or between 99% and 100%.

[0137] In some embodiments, the relative humidity of the flue gas stream is between 95% and 96%, between 95% and 97%, between 95% and 98%, between 95% and 99%, or between 95% and 100%.

[0138] In some embodiments, the flue gas stream comprises at least one SO x Contains no compounds.

[0139] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of at least 1 ppm, at least 5 ppm, at least 10 ppm, at least 20 ppm, at least 25 ppm, at least 30 ppm, at least 35 ppm, at least 40 ppm, at least 45 ppm, at least 50 ppm, at least 100 ppm, at least 300 ppm, at least 500 ppm, or at least 1000 ppm. x Contains compounds.

[0140] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of at least 1 ppm to 200 ppm, 5 ppm to 200 ppm, 10 ppm to 200 ppm, 50 ppm to 200 ppm, or 100 ppm to 200 ppm. x Contains compounds.

[0141] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of between 20 ppm and 100 ppm, between 25 ppm and 100 ppm, between 30 ppm and 100 ppm, between 35 ppm and 100 ppm, between 40 ppm and 100 ppm, between 45 ppm and 100 ppm, between 50 ppm and 100 ppm, between 55 ppm and 100 ppm, between 60 ppm and 100 ppm, between 65 ppm and 100 ppm, between 70 ppm and 100 ppm, between 75 ppm and 100 ppm, between 80 ppm and 100 ppm, between 85 ppm and 100 ppm, between 90 ppm and 100 ppm, or between 95 ppm and 100 ppm. x Contains compounds.

[0142] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of from 20 ppm to 25 ppm, from 20 ppm to 30 ppm, from 20 ppm to 35 ppm, from 20 ppm to 40 ppm, from 20 ppm to 45 ppm, from 20 ppm to 50 ppm, from 20 ppm to 55 ppm, from 20 ppm to 60 ppm, from 20 ppm to 65 ppm, from 20 ppm to 70 ppm, from 20 ppm to 75 ppm, from 20 ppm to 80 ppm, from 20 ppm to 85 ppm, from 20 ppm to 90 ppm, from 20 ppm to 95 ppm, or from 20 ppm to 100 ppm. x Contains compounds.

[0143] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of from 1 ppm to 90 ppm, from 1 ppm to 80 ppm, from 1 ppm to 70 ppm, from 1 ppm to 90 ppm, from 1 ppm to 90 ppm, from 1 ppm to 60 ppm, from 1 ppm to 50 ppm, from 1 ppm to 40 ppm, from 1 ppm to 30 ppm, from 1 ppm to 20 ppm, from 1 ppm to 10 ppm, or from 1 ppm to 5 ppm. x Contains compounds.

[0144] In some embodiments, the flue gas stream is free of mercury vapor.

[0145] In some embodiments, the flue gas stream has at least 1 μg / m of the flue gas stream. 3 , at least 2 μg / m of the flue gas stream 3 , at least 3 μg / m of the flue gas stream 3 , at least 4 μg / m of the flue gas stream 3 , at least 5 μg / m of the flue gas stream 3 , at least 6 μg / m of the flue gas stream 3 , at least 7 μg / m of the flue gas stream 3 , at least 8 μg / m of the flue gas stream 3 , at least 9 μg / m of the flue gas stream 3 , at least 10 μg / m of the flue gas stream 3 , at least 15 μg / m of the flue gas stream 3 , at least 20 μg / m of the flue gas stream 3or at least 50 μg / m of the flue gas stream 3 Contains mercury vapor at a concentration of.

[0146] In some embodiments, the flue gas stream has a concentration of at least 1 μg / m of the flue gas stream. 3 ~50μg / m 3 , 5 μg / m of flue gas stream 3 ~50μg / m 3 , 10 μg / m of flue gas stream 3 ~50μg / m 3 , 20 μg / m of flue gas stream 3 ~50μg / m 3 or 40 μg / m of the flue gas stream. 3 ~50μg / m 3 Contains mercury vapor at a concentration of.

[0147] In some embodiments, the flue gas stream has a concentration of at least 1 μg / m of the flue gas stream. 3 ~10μg / m 3 , 2 μg / m of flue gas stream 3 ~10μg / m 3 , 3 μg / m of flue gas stream 3 ~10μg / m 3 , 4 μg / m of flue gas stream 3 ~10μg / m 3 , 5 μg / m of flue gas stream 3 ~10μg / m 3 , 6 μg / m of flue gas stream 3 ~10μg / m 3 , 7 μg / m of flue gas stream 3 ~10μg / m 3 , 8 μg / m of flue gas stream 3 ~10μg / m 3 , 9 μg / m of flue gas stream 3 ~10μg / m 3 Contains mercury vapor at a concentration of.

[0148] In some embodiments, the flue gas stream has a concentration of at least 1 μg / m of the flue gas stream. 3 ~2μg / m 3 , 1 μg / m of flue gas stream 3 ~3μg / m 3 , 1 μg / m of flue gas stream3 ~4μg / m 3 , 1 μg / m of flue gas stream 3 ~5μg / m 3 , 1 μg / m of flue gas stream 3 ~6μg / m 3 , 1 μg / m of flue gas stream 3 ~7μg / m 3 , 1 μg / m of flue gas stream 3 ~8μg / m 3 or 1 μg / m of the flue gas stream. 3 ~9μg / m 3 Contains mercury vapor at a concentration of.

[0149] In some embodiments, the at least one permeation control material comprises polycarbonate (PC), ethyl cellulose (EC), polystyrene (PS), polystyrene-divinylbenzene (PS-DVB), polyacrylonitrile (PAN), polyvinylidene chloride (PVDC), polyvinylidene fluoride (PVDF), polyvinylidene fluoride copolymer with perfluoropropylene, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polychlorotrifluoroethylene (PCTFE), cross-linked epoxy, or a combination thereof. In some embodiments, the at least one permeation control material comprises polyvinyl chloride (PVC), chlorinated polyvinyl chloride (CPVC), at least one polyolefin, or any combination thereof. In some embodiments, the at least one polyolefin comprises polyethylene, an example of which is ultra-high molecular weight (UHMW) polyethylene, polypropylene, polybutylene, or any combination thereof.

[0150] In some embodiments, the PVDF copolymer is a copolymer of PVDF and hexafluoropropylene (HFP).

[0151] Non-limiting commercial examples of PVDF homopolymers or copolymers suitable for some embodiments of the present disclosure include, but are not limited to, Kynar Flex® and Kynar Superflex®, each commercially available from Arkema.

[0152] In some embodiments, the permeation control material may be in the form of an adhesive layer, a discontinuous film such as a net, a continuous film, or any combination thereof. In some embodiments, the permeation control material is an adhesive layer. In some embodiments, the permeation control material is a PVDF adhesive layer in the form of a net, such as the non-limiting example described in Example 1 below. In some embodiments, the permeation control material is a PVDF adhesive layer in the form of a continuous film, such as the non-limiting example described in Example 1 below.

[0153] In some embodiments, the at least one permeation control material is in the form of at least one permeation control layer, the at least one permeation control layer being disposed between the first SPC layer and the halogen reservoir, between the second SPC layer and the halogen reservoir, or both.

[0154] In some embodiments, the article further comprises 1-20 permeation control layers, and the permeation control layers are disposed between the SPC layer and the halogen reservoir.

[0155] In some embodiments, the article further comprises one permeation control layer, and the permeation control layer is disposed between the SPC layer and the halogen reservoir. In some embodiments, the article further comprises two permeation control layers, three permeation control layers, four permeation control layers, five permeation control layers, six permeation control layers, seven permeation control layers, eight permeation control layers, nine permeation control layers, ten permeation control layers, fifteen permeation control layers, or twenty permeation control layers, and the permeation control layers are disposed between the SPC layer and the halogen reservoir.

[0156] In some embodiments, the article further comprises 1-15 permeation control layers, 1-10 permeation control layers, 1-9 permeation control layers, 1-8 permeation control layers, 1-7 permeation control layers, 1-6 permeation control layers, 1-5 permeation control layers, 1-4 permeation control layers, 1-3 permeation control layers, or 1-2 permeation control layers, wherein the permeation control layers are disposed between the SPC layer and the halogen reservoir.

[0157] In some embodiments, the article further comprises 2-20 permeation control layers, 3-20 permeation control layers, 4-20 permeation control layers, 5-20 permeation control layers, 6-20 permeation control layers, 7-20 permeation control layers, 8-20 permeation control layers, 9-20 permeation control layers, 10-20 permeation control layers, or 15-20 permeation control layers.

[0158] In some embodiments, the halogen reservoir comprises the at least one permeation control material and the at least one halogen source. In some embodiments, the at least one halogen source and the at least one permeation control material are present within a halogen reservoir. In some embodiments, the at least one halogen source and the at least one permeation control material form an integral part of the halogen reservoir. In some embodiments, the halogen reservoir consists essentially of the at least one permeation control material and the at least one halogen source. In some embodiments, the halogen reservoir consists of the at least one permeation control material and the at least one halogen source.

[0159] In some embodiments, the halogen reservoir is a third SPC layer.In some embodiments, the halogen reservoir comprises at least one permeation control material.

[0160] In some embodiments, the halogen reservoir comprises 5 wt% to 95 wt% of at least one permeation control material, based on the total weight of the halogen reservoir.

[0161] In some embodiments, the halogen reservoir comprises 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, or 95 wt% of at least one permeation control material based on the total weight of the halogen reservoir.

[0162] In some embodiments, the halogen reservoir comprises between 10 wt% and 95 wt%, 15 wt% and 95 wt%, 20 wt% and 95 wt%, 25 wt% and 95 wt%, 30 wt% and 95 wt%, 35 wt% and 95 wt%, 40 wt% and 95 wt%, 45 wt% and 95 wt%, 50 wt% and 95 wt%, 55 wt% and 95 wt%, 60 wt% and 95 wt%, 65 wt% and 95 wt, 70 wt% and 95 wt%, 75 wt% and 95 wt, 80 wt% and 95 wt%, 85 wt% and 95 wt%, or 90 wt% and 95 wt% of at least one permeation control material, based on the total weight of the halogen reservoir.

[0163] In some embodiments, the halogen reservoir comprises between 5 wt% and 10 wt%, between 5 wt% and 15 wt%, between 5 wt% and 20 wt%, between 5 wt% and 25 wt%, between 5 wt% and 30 wt%, between 5 wt% and 35 wt%, between 5 wt% and 40 wt%, between 5 wt% and 45 wt%, between 5 wt% and 50 wt%, between 5 wt% and 55 wt%, between 5 wt% and 60 wt%, between 5 wt% and 65 wt%, between 5 wt% and 70 wt%, between 5 wt% and 75 wt%, between 5 wt% and 80 wt%, between 5 wt% and 85 wt%, or between 5 wt% and 90 wt% of at least one permeation control material, based on the total weight of the halogen reservoir.

[0164] In some embodiments, the halogen reservoir comprises at least one halogen source, based on the total weight of the halogen reservoir. In some embodiments, the halogen source comprises 0.1 wt% to 50 wt% of at least one halogen source, based on the total weight of the halogen reservoir.

[0165] In some embodiments, the halogen reservoir comprises 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, or 0.5 wt% of at least one halogen source based on the total weight of the halogen reservoir. In some embodiments, the halogen reservoir comprises 1 wt%, 2 wt%, 3 wt%, 4 wt%, or 5 wt% of at least one halogen source based on the total weight of the halogen reservoir. In some embodiments, the halogen reservoir comprises 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, or 50 wt% of at least one halogen source based on the total weight of the halogen reservoir.

[0166] In some embodiments, the halogen reservoir comprises between 0.1 wt% and 50 wt%, between 0.2 wt% and 50 wt%, between 0.3 wt% and 50 wt%, between 0.4 wt% and 50 wt%, between 0.5 wt% and 50 wt%, between 1 wt% and 50 wt%, between 2 wt% and 50 wt%, between 3 wt% and 50 wt%, between 4 wt% and 50 wt%, between 5 wt% and 50 wt%, between 10 wt% and 50 wt%, between 15 wt% and 50 wt%, between 20 wt% and 50 wt%, between 25 wt% and 50 wt%, between 30 wt% and 50 wt%, between 35 wt% and 50 wt%, between 40 wt% and 50 wt%, or between 45 wt% and 50 wt% of at least one halogen source, based on the total weight of the halogen reservoir.

[0167] In some embodiments, the halogen reservoir comprises between 0.1 wt% and 45 wt%, between 0.1 wt% and 40 wt%, between 0.1 wt% and 35 wt%, between 0.1 wt% and 30 wt%, between 0.1 wt% and 25 wt%, between 0.1 wt% and 20 wt%, between 0.1 wt% and 15 wt%, between 0.1 wt% and 10 wt%, between 0.1 wt% and 5 wt%, between 0.1 wt% and 1 wt%, between 0.1 wt% and 0.5 wt%, between 0.1 wt% and 0.4 wt%, between 0.1 wt% and 0.3 wt%, or between 0.1 wt% and 0.2 wt% of at least one halogen source, based on the total weight of the halogen reservoir.

[0168] In some embodiments, the at least one halogen source comprises a metal halide, an ammonium halide, an elemental halogen, or any combination thereof. In some embodiments, the at least one halogen source comprises a metal halide. In some embodiments, the at least one halogen source is selected from at least one of sodium chloride, potassium chloride, sodium bromide, potassium bromide, sodium iodide, or potassium iodide. In some embodiments, the at least one halogen source comprises an ammonium halide. In some embodiments, the at least one halogen source is selected from at least one of tetramethylammonium iodide, tetrabutylammonium iodide, tetraethylammonium iodide, tetrapropylammonium iodide, tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, tetrabutylammonium triiodide, tetrabutylammonium tribromide, or any combination thereof. In some embodiments, the at least one halogen source comprises an elemental halogen. In some embodiments, the at least one halogen source is selected from at least one of elemental iodine (I2), elemental chlorine (Cl2), or elemental bromine (Br2).

[0169] In some embodiments, the at least one halogen source is elemental iodine (I2). In some embodiments, the at least one halogen source is tetrabutylammonium iodide (TBAI). In some embodiments, the at least one halogen source is potassium iodide (KI).

[0170] In some embodiments, the at least one halogen source comprises at least one phosphonium halide. In some embodiments, the at least one phosphonium halide comprises tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI3), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), or any combination thereof. In some embodiments, the at least one phosphonium halide is selected from the group consisting of tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI3), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), and any combination thereof.

[0171] In some embodiments, the at least one phosphonium halide comprises tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI3), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), or any combination thereof. In some embodiments, the at least one phosphonium halide is selected from the group consisting of tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI3), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), and any combination thereof.

[0172] In some embodiments, the at least one phosphonium halide is ethyltriphenylphosphonium iodide (ETPPI).

[0173] In some embodiments, the at least one halogen source may be incorporated into the SPC by any suitable technique, including, but not limited to, imbibing, impregnating, adsorbing, mixing, sprinkling, spraying, dipping, painting, coating, ion exchange, or otherwise applying the at least one halogen source to the SPC. In some embodiments, the halogen source may be disposed within the SPC, for example, within any pores of the SPC. In some embodiments, the at least one halogen source may be provided in a solution, which may be contacted in situ with the SPC under system operating conditions.

[0174] Additional forms of the sorbent-polymer complexes described herein are described in U.S. Patent No. 9,827,551 to Hardwick et al., and U.S. Patent No. 7,442,352 to Lu et al., each of which is incorporated herein by reference in its entirety.

[0175] In some embodiments, the halogen reservoir is configured to release the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.01% to 0.3% of the total halogen per day.

[0176] In some embodiments, the halogen reservoir is configured to release the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.01%, 0.02%, or 0.05% of the total halogen per day. In some embodiments, the halogen reservoir is configured to release the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.1%, 0.2%, or 0.3% of the total halogen per day.

[0177] In some embodiments, the halogen reservoir is configured to release the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.01%-0.2% / day, 0.01%-0.1% / day, 0.01%-0.05% / day, or 0.01%-0.02% / day of the total halogen.

[0178] In some embodiments, the halogen reservoir is configured to release the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.02%-0.3% / day, 0.05%-0.3% / day, 0.1%-0.3% / day, or 0.2%-0.3% / day of the total halogen.

[0179] In some embodiments, at least one of the first SPC layer or the second SPC layer can also include at least one halogen source.

[0180] In some embodiments, the at least one halogen source of the first SPC layer, or the at least one halogen source of the second SPC layer, or both, is the same as the at least one halogen source of the halogen reservoir. In some embodiments, the at least one halogen source within the first SPC layer, or the at least one halogen source within the second SPC layer, is different from the at least one halogen source of the halogen reservoir.

[0181] In some embodiments, the at least one halogen source may be dissociably bound to at least one polymer chain of the at least one permeation control material. In some embodiments, "dissociably bound" means that the at least one halogen source may have an inherent binding affinity (binding adsorption ability) to the at least one permeation control material. In some embodiments, this binding efficiency is sufficient to produce any release rate or range of the at least one halogen source from the at least one permeation control material described herein. In some embodiments, the at least one halogen source may become bound to the at least one permeation control material via solution dispersion.

[0182] In some embodiments, the bond adsorption capacity between the at least one permeation control material and the at least one halogen source is 5% to 50% by weight, 10% to 50% by weight, 25% to 50% by weight, or 45% to 50% by weight.

[0183] In some embodiments, the bond adsorption capacity between the at least one permeation control material and the at least one halogen source is between 5% and 45% by weight, between 5% and 25% by weight, or between 5% and 10% by weight.

[0184] In some embodiments, the bond adsorption capacity between the at least one permeation control material and the at least one halogen source is between 10% and 45% by weight, between 10% and 25% by weight, or between 25% and 45% by weight.

[0185] The binding adsorption capacity can be determined by a gravimetric capacity test.

[0186] In some embodiments, the halogen reservoir further comprises particles embedded within the halogen reservoir.

[0187] The particles may comprise any suitable material, for example, in some embodiments, the particles may comprise activated carbon derived from coal, lignite, wood, coconut shell, another carbonaceous material, silica gel, zeolite, or any combination thereof.

[0188] In some embodiments, the particles comprise carbon particles. In some embodiments, the carbon particles may comprise any type of carbon particles listed herein (e.g., coal, activated carbon derived from wood).

[0189] In some embodiments, the particles are present in the halogen reservoir, the permeation control layer, or any combination thereof in an amount of 1 wt% to 75 wt%, based on the total weight of the halogen reservoir, the permeation control layer, or any combination thereof. In some embodiments, the particles are present in the halogen reservoir, the permeation control material, or any combination thereof in an amount of 25 wt% to 75 wt%, based on the total weight of the halogen reservoir, the permeation control material, or any combination thereof. In some embodiments, the particles are present in the halogen reservoir, the permeation control material, or any combination thereof in an amount of 50 wt% to 75 wt%, based on the total weight of the halogen reservoir, the permeation control material, or any combination thereof.

[0190] In some embodiments, the particles are present in the halogen reservoir, the permeation control material, or any combination thereof in an amount of 1 wt% to 50 wt%, based on the total weight of the halogen reservoir, the permeation control material, or any combination thereof. In some embodiments, the particles are present in the halogen reservoir, the permeation control material, or any combination thereof in an amount of 1 wt% to 25 wt%, based on the total weight of the halogen reservoir, the permeation control material, or any combination thereof.

[0191] In some embodiments, the particles are present in the halogen reservoir, the permeation control material, or any combination thereof, in an amount of 25 wt% to 50 wt%, based on the total weight of the halogen reservoir, the permeation control material, or any combination thereof.

[0192] In some embodiments in which the particles comprise activated carbon, the activated carbon is present in the halogen reservoir in an amount between 0.1 wt % and 60 wt %, based on the total weight of the halogen reservoir.

[0193] In some embodiments, the activated carbon is present in the halogen reservoir in an amount of 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, or 0.9 wt%, based on the total weight of the halogen reservoir. In some embodiments, the activated carbon is present in the halogen reservoir in an amount of 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, or 60 wt%, based on the total weight of the halogen reservoir.

[0194] In some embodiments, the activated carbon is present in the halogen reservoir in an amount between 0.2 wt% and 60 wt%, between 0.3 wt% and 60 wt%, between 0.4 wt% and 60 wt%, between 0.5 wt% and 60 wt%, between 0.6 wt% and 60 wt%, between 0.7 wt% and 60 wt%, between 0.8 wt% and 60 wt%, or between 0.9 wt% and 60 wt%, based on the total weight of the halogen reservoir. In some embodiments, the activated carbon is present in the halogen reservoir in an amount between 1 wt% and 60 wt%, between 5 wt% and 60 wt%, between 10 wt% and 60 wt%, between 15 wt% and 60 wt%, between 20 wt% and 60 wt%, between 25 wt% and 60 wt%, between 30 wt% and 60 wt%, between 35 wt% and 60 wt%, between 40 wt% and 60 wt%, between 45 wt% and 60 wt%, between 50 wt% and 60 wt%, or between 55 wt% and 60 wt%, based on the total weight of the halogen reservoir.

[0195] In some embodiments, the activated carbon is present in the halogen reservoir at a concentration of 0.1 wt% to 55 wt%, 0.1 wt% to 50 wt%, 0.1 wt% to 45 wt%, 0.1 wt% to 40 wt%, 0.1 wt% to 35 wt%, 0.1 wt% to 30 wt%, 0.1 wt% to 25 wt%, 0.1 wt% to 20 wt%, 0.1 wt% to 15 wt%, based on the total weight of the halogen reservoir. t%, 0.1wt% to 10wt%, 0.1wt% to 5wt%, 0.1wt% to 1wt%, 0.1wt% to 0.9wt%, 0.1wt% to 0.8wt%, 0.1wt% to 0.7wt%, 0.1wt% to 0.6wt%, 0.1wt% to 0.5wt%, 0.1wt% to 0.4wt%, 0.1wt% to 0.3wt%, or 0.1wt% to 0.2wt%.

[0196] In some embodiments, the at least one halogen source is present within the activated carbon of the halogen reservoir. In some embodiments, the halogen reservoir includes a third SPC. In some embodiments, the at least one halogen source fills the SPC of the halogen reservoir.

[0197] In some embodiments, the sorbent of the halogen reservoir comprises the same material as at least one of the first sorbent or the second sorbent. In some embodiments, the sorbent of the halogen reservoir comprises a different material than at least one of the first sorbent or the second sorbent.

[0198] In some embodiments, the polymer of the halogen reservoir comprises the same material as at least one of the first polymer (corresponding to the first SPC layer) or the second polymer (corresponding to the second SPC layer). In some embodiments, the polymer of the halogen reservoir comprises a different material than at least one of the first polymer (corresponding to the first SPC layer) or the second polymer (corresponding to the second SPC layer).

[0199] In some embodiments, there is at least one permeation control layer positioned between the halogen reservoir and the first SPC layer. In some embodiments, there is at least one permeation control layer positioned between the halogen reservoir and the second SPC layer. In some embodiments, there is at least one permeation control layer positioned between the halogen reservoir and the first SPC layer and at least one permeation control layer positioned between the halogen reservoir and the second SPC layer.

[0200] In some embodiments, the at least one permeation control layer has a thickness of from 1 μm to 1000 μm.

[0201] In some embodiments, the thickness of the at least one transmission control layer is 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, or 1000 μm.

[0202] The thickness of the at least one transmission control layer can be measured using cross-sectional scanning electron microscopy.

[0203] In some embodiments, the thickness of the at least one transmission control layer is 5 μm to 1000 μm, 10 μm to 1000 μm, 20 μm to 1000 μm, 30 μm to 1000 μm, 40 μm to 1000 μm, 50 μm to 1000 μm, 100 μm to 1000 μm, 200 μm to 1000 μm, 300 μm to 1000 μm, 400 μm to 1000 μm, 500 μm to 1000 μm, 600 μm to 1000 μm, 700 μm to 1000 μm, 800 μm to 1000 μm, or 900 μm to 1000 μm.

[0204] In some embodiments, the at least one transmission control layer has a thickness of 1 μm to 900 μm, 1 μm to 800 μm, 1 μm to 700 μm, 1 μm to 600 μm, 1 μm to 500 μm, 1 μm to 400 μm, 1 μm to 300 μm, 1 μm to 200 μm, 1 μm to 100 μm, 1 μm to 50 μm, 1 μm to 40 μm, 1 μm to 30 μm, 1 μm to 20 μm, 1 μm to 10 μm, or 1 μm to 5 μm.

[0205] In some embodiments, the at least one transmission control layer has a thickness of 25 μm to 500 μm.In some embodiments, the at least one transmission control layer has a thickness of 125 μm to 250 μm.

[0206] In some embodiments, the at least one transmission control layer comprises at least one transmission control material.

[0207] In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.01% to 0.3% of total halogen per day.

[0208] In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.01% of the total halogen per day. In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.02% of the total halogen per day. In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.05% of the total halogen per day. In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.1% of the total halogen per day. In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.2% of the total halogen per day. In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.3% of the total halogen per day.

[0209] In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.01%-0.2% / day, 0.01%-0.1% / day, 0.01%-0.05% / day, or 0.01%-0.02% / day of the total halogen.

[0210] In some embodiments, the at least one permeation control layer is configured to release the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.02%-0.3% / day, 0.05%-0.3% / day, 0.1%-0.3% / day, or 0.2%-0.3% / day of the total halogen.

[0211] In some embodiments, the at least one permeation control layer is configured to delay release of the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.01% to 0.3% of total halogen per day.

[0212] In some embodiments, the at least one permeation control layer is configured to delay release of the at least one halogen source into at least one of the first or second SPC layers at a rate of 0.01%, 0.02%, 0.05%, 0.1%, 0.2%, or 0.3% of total halogen per day.

[0213] In some embodiments, the at least one permeation control layer is configured to delay release of the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.01%-0.2%, 0.01%-0.1%, 0.01%-0.05%, or 0.01%-0.02% of the total halogen per day.

[0214] In some embodiments, the at least one permeation control layer is configured to delay release of the at least one halogen source into at least one of the first SPC layer or the second SPC layer at a rate of 0.02%-0.3%, 0.05%-0.3%, 0.1%-0.3%, or 0.2%-0.3% of the total halogen per day.

[0215] Some embodiments of the present disclosure relate to a method that includes obtaining an exemplary article disclosed herein and exposing the article to a flue gas stream, hi some embodiments, the flue gas stream includes at least one of sulfur oxides, mercury vapor, or any combination thereof.

[0216] In some embodiments, the method includes forming an article by disposing a halogen reservoir between a first SPC layer and a second SPC layer to produce a layered structure.

[0217] In some embodiments, the method includes adhering the layered structure together, which in some embodiments may include any suitable form of attachment, such as, for example, laminating, gluing, pressing, sewing, stitching, thermal bonding, laser bonding, welding, laminating, using at least one adhesive, or any combination thereof.

[0218] In some embodiments, the article comprises at least one permeation control material in the form of at least one permeation control layer, and the step of disposing a halogen reservoir between the first SPC layer and the second SPC layer further comprises disposing the at least one permeation control layer between the first SPC layer and the halogen reservoir, disposing the at least one permeation control layer between the second SPC layer and the halogen reservoir, or any combination thereof.

[0219] In some embodiments, the step of disposing a halogen reservoir between the first SPC layer and the second SPC layer includes disposing a first layer of the at least one permeation control material between the first SPC layer and the halogen reservoir, and disposing a second layer of the at least one permeation control material between the second SPC layer and the halogen reservoir.

[0220] In some embodiments, the halogen reservoir comprises at least one permeation control material. In some embodiments, the article is formed by combining at least one halogen source and at least one permeation control material to form a halogen reservoir, disposing the halogen reservoir between a first SPC layer and a second SPC layer to produce a layered structure, and adhering the layered structure together. In some embodiments, the attachment may include any suitable form of attachment, such as, for example, thermal bonding, laser bonding, welding, lamination, the use of at least one adhesive, or any combination thereof. In some embodiments, the at least one adhesive may be the at least one permeation control material, as described herein.

[0221] In some embodiments, combining the at least one halogen source with the at least one permeation control material comprises heating the at least one permeation control material to a temperature sufficient to melt the at least one permeation control material, and mixing the at least one molten permeation control material with the at least one halogen source.

[0222] In some embodiments, the temperature sufficient to melt the at least one permeation control material corresponds to the melting temperature of at least one permeation control material or combination of permeation control materials described herein.

[0223] In some embodiments, the temperature sufficient to melt the at least one permeation control material is between 80° C. and 300° C. In some embodiments, the temperature sufficient to melt the at least one permeation control material is between 100° C. and 300° C. In some embodiments, the temperature sufficient to melt the at least one permeation control material is between 200° C. and 300° C.

[0224] In some embodiments, the temperature sufficient to melt the at least one permeation control material is between 80° C. and 200° C. In some embodiments, the temperature sufficient to melt the at least one permeation control material is between 80° C. and 100° C.

[0225] In some embodiments, the temperature sufficient to melt the at least one permeation control material is between 90° C. and 220° C. In some embodiments, the temperature sufficient to melt the at least one permeation control material is between 130° C. and 180° C.

[0226] In some embodiments, the at least one halogen source is mixed with the at least one molten permeation control material. In some embodiments, the at least one halogen source is mixed with the at least one molten permeation control material as a suspension, a solution, an emulsion, a dispersion, or any combination thereof.

[0227] In some embodiments, the at least one halogen source is mixed with the at least one molten permeation control material in the vapor phase.

[0228] In some embodiments, combining the at least one halogen source with the at least one permeation control material comprises dissolving the at least one permeation control material in a solvent to form a mixture, adding at least one halogen source to the mixture of solvent and the at least one permeation control material, and evaporating the solvent.

[0229] In some embodiments, the solvent may be methylene chloride (DCM), tetrahydrofuran (THF), ethyl acetate (EtOAc), acetone, toluene, or any combination thereof.

[0230] In some embodiments, the method further comprises adding particles to the mixture of the at least one halogen source, the solvent, and the permeation control material. In some embodiments, the particles can be any of the particles described herein, such as carbon particles.

[0231] In some embodiments, combining the at least one halogen source with the at least one permeation control material comprises obtaining at least one halogen source and forming a chemical complex with the at least one halogen source and the at least one permeation control material. In some embodiments, the chemical complex may comprise a charge transfer complex of elemental iodine with an aromatic ring, such as that found in polystyrene.

[0232] In some embodiments, the at least one halogen source forms a chemical complex with the at least one permeation control material while the at least one halogen source is in solution. In some embodiments, the at least one halogen source forms a chemical complex with the at least one permeation control material while the at least one halogen source is in the gas phase.

[0233] In some embodiments, the article comprises a second permeation control material, the second permeation control material being in the form of at least one layer of the second permeation control material, and the method comprises disposing the at least one layer of the second permeation control material between a first SPC layer and the halogen reservoir, disposing the at least one layer of the second permeation control material between a second SPC layer and the halogen reservoir, or any combination thereof.

[0234] In some embodiments, the method further includes disposing a first layer of a second permeation control material between the first SPC layer and the halogen reservoir, and disposing a second layer of a second permeation control material between the second SPC layer and the halogen reservoir.

[0235] Some embodiments of the present disclosure relate to a system including any of the exemplary articles and / or embodiments of the articles disclosed herein. In some embodiments, the system includes a passageway configured for the passage of a gas stream. In some embodiments, the article is housed within the passageway. In some embodiments, at least one of the first layer or the second layer of the article is disposed between a reservoir and the gas stream.

[0236] In some embodiments, the system can include several articles formed within a plurality of passages. In such embodiments, a gas stream can flow between the passages such that the gas stream directly contacts either the first layer or the second layer, but not directly contacts the reservoir. In some embodiments, the plurality of passages in the device can facilitate the flow of reactants, e.g., gaseous components, over one or more surfaces of the system and the discharge of at least one liquid product.

[0237] Non-limiting exemplary geometries of systems including the examples described herein can be found in U.S. Patent No. 9,381,459 to Stark et al., which is incorporated herein by reference in its entirety for all purposes.

[0238] 1 depicts a non-limiting embodiment of the articles described herein. As depicted, article 100 can include a first sorbent polymer composite layer 101, a second sorbent polymer composite layer 102, and a halogen reservoir 103 that includes at least one halogen source (not shown).

[0239] 2A illustrates a further non-limiting embodiment of the articles described herein. As shown, article 200 can include a first sorbent polymer composite layer 201, a second sorbent polymer composite layer 202, and a halogen reservoir layer 203. The halogen reservoir layer includes a third sorbent polymer composite loaded with at least one halogen source (not shown). In some non-limiting embodiments, first sorbent polymer composite layer 201 and second sorbent polymer composite layer 202 can also be loaded with at least one halogen source (not shown).

[0240] 2B illustrates a further non-limiting embodiment of article 200. As shown, in some embodiments, article 200 can also include a first permeation control layer 204 and a second permeation control layer 205. The first permeation control layer 204 is disposed between the first sorbent polymer composite layer 201 and the halogen reservoir layer 203. The second permeation control layer 205 is disposed between the second sorbent polymer composite layer 202 and the halogen reservoir layer 203.

[0241] 3A illustrates another non-limiting embodiment of the articles described herein. As shown, article 300 can include a first sorbent polymer composite layer 301, a second sorbent polymer composite layer 302, and a halogen reservoir 303. Halogen reservoir 303 includes at least one permeation control material and is filled with at least one halogen source (not shown).

[0242] 3B illustrates a further non-limiting embodiment of the article 300. As shown, in some embodiments, the article 300 can also include a first transmission control layer 304 and a second transmission control layer 305.

[0243] 3C illustrates another non-limiting embodiment of the article 300. As shown, in some embodiments, the article 300 can include particles 306 within the halogen reservoir 303.

[0244] 3D illustrates a further non-limiting embodiment of the article 300. As shown, in some embodiments, the article 300 can also include a first permeation control layer 304, a second permeation control layer 305, and particles 306 within the halogen reservoir 303.

[0245] FIG. 4 illustrates a non-limiting embodiment of a pollution control system 400 having at least one of the articles described herein. Some non-limiting applications of the pollution control system 400 may be for controlling air pollutant emissions to comply with various air pollutant emission standards. The pollution control system 400 may be configured to capture elemental mercury and oxidized gas phase mercury from industrial flue gases. The pollution control system 400 may include discrete stackable modules 402. These modules may be downstream of a particle collection system. In some embodiments, the modules 402 may be configured to include one or more embodiments of the articles 404 (shown in an enlarged partial view in FIG. 4) described herein.

[0246] FIG. 5 is a schematic diagram 500 showing a flue gas stream flowing over a non-limiting embodiment of an article 502 described herein. The article 502 can capture both elemental and oxidized mercury from the flue gas stream as it flows past (e.g., over or through the material of the article 502). Mercury can be fixedly bound within the material of the article 502 via chemisorption. SO2 can also be adsorbed and / or absorbed and catalyzed (via a SO2 oxidation catalyst) to liquid sulfuric acid. The liquid sulfuric acid can form droplets 504 and be expelled from the article 502. The droplets 504 can flow downward via gravity acting on the surface of the article 502.

[0247] Various examples and comparative examples of the article were tested to demonstrate the improved properties of the embodiments of the article incorporated within the embodied systems and processes also described herein, the results of which are detailed below.

[0248] Test Method

[0249] Simulated combustion exhaust gas flow durability test

[0250] The Simulated Flue Gas Stream Durability Test is a laboratory test. An exemplary test for simulated exposure to flue gas streams was conducted using an apparatus including: (1) A supply of air regulated by a mass flow controller; a source of SO2 provided by a gas cylinder containing a 1% sulfur dioxide / nitrogen mixture regulated through a mass flow controller; (2) A triangular sample cell with a side length of 12 mm and equipped with a bypass. This was placed in a furnace maintained at 65°C. (3) Maintain high relative humidity (>80%) using an MH-070 permeable tube humidifier (PermaPure, NJ, USA).

[0251] 300 ppm (786 mg / m 3 The samples were exposed to a simulated flue gas stream containing 100% CO2 and 90% humidity in the above apparatus at 1 standard liter / min for a period of approximately 3 months. The test period may vary and may be greater or less than 3 months. The total halogen content of the samples was measured over time by X-ray fluorescence ("XRF") in wt %. The total halogen content of the disclosed samples was determined as the total iodine content. Thus, discussion of halogen content and release rate is based on the iodine content of the sample and the release rate of total iodine (total halogens).

[0252] The relative iodine content was followed over time according to the formula C_iodine / C_iodine_0, where C_iodine / C_iodine_0 is the total iodine content in the article at a given time point relative to the initial total iodine content in the article.

[0253] The release rate of total halogens was analyzed by following the relative iodine content using an exponential release rate (decay) function according to the equation C_iodine / C_iodine_0 = exp(-k*time), where C_iodine is the total iodine content measured in each sample over time, C_iodine_0 is the initial total iodine content, and k is the iodine release rate constant with units of % / day.

[0254] The total release rate is equal to k*C_iodine and the relative release rate is equal to k*C_iodine / C_iodine_0.

[0255] The total release rate is equal to the release rate constant (e.g., 0.5% / day) multiplied by the total halogen in the article. In other words, the release rate of the total halogen from the article is, in this example, 0.5% of the total halogen in the article per day. The relative release rate and the release rate constant have the same units (% / day), but differ in value depending on the relative iodine content. The iodine content was also tracked over time according to the formula C_iodine = C_iodine_0 * exp(-k*time), where C_iodine is the iodine content in the article, C_iodine_0 is the initial total iodine content, and k is the same iodine release rate (decay) constant as above, with units of % / day.

[0256] An exponential release rate (decay) model was used to estimate the depletion of the halogen source over time.

[0257] Combustion exhaust gas flow durability test

[0258] The flue gas stream durability test is a field test. An exemplary test was conducted in which a sorbent polymer composite (SPC) laminate sample (representing an article of the present disclosure) was exposed to a slipstream of a wet flue gas stream downstream from a desulfurization absorber at a coal-fired power plant, exposing the sample to the flue gas stream in two different configurations.

[0259] For the first configuration, six 3.5" x 12" (8.89 cm x 30.48 cm) sorbent polymer composite (SPC) laminate sheets were mounted into a 3.5" x 3.5" x 40" (8.89 cm x 8.89 cm x 101 cm) insulating sample fixture, supported on rods to allow unimpeded flow across the sheets. Approximately 80 ACFM (actual cubic feet per minute) (137 m 3 The samples were exposed to a flue gas flow of 1000 sq. m. / hr drawn by a fan through a series of tubes and into the sample fixture.

[0260] For the second configuration, a 1.25" x 12" (3.175 cm x 30.48 cm) Sorbent Polymer Composite (SPC) laminate strip was mounted onto a frame fixture 2' x 2' x 1' (61 cm x 61 cm x 30 cm) while the top and bottom of the strip were secured in place along rails of a frame capable of holding up to 100 strips. These rails were separated by 2 inches (50 mm) to provide unimpeded flow across the frame. The frame was inserted into a 2.1' x 2.1' x 8' (0.66 m x 0.66 m x 2.4 m) insulated Pilot Tower Unit. Approximately 2880 ACFM (4860 m 3 The samples were exposed to a flue gas flow of 1000000 / hr using a fan.

[0261] Samples according to the present disclosure were tested in the first configuration or the second configuration or both.

[0262] In both configurations, the flow rate and pressure differential were monitored across the sample fixture. By nature, the composition of the flue gas stream was highly variable, but a typical composition of the flue gas stream was between 2 μg / m mercury and 100 μg / m 3 The SO2 concentration was 20-40 ppm, the O2 concentration was 6%, the NO concentration was 200 ppm, and the relative humidity was >95%. The temperature of the slipstream flue gas stream was 50-55 °C.

[0263] Samples were taken approximately once a month (every 30 days) and the samples were analyzed for total halogen content (wt%) by X-ray fluorescence ("XRF"). The total halogen content of the disclosed samples was determined as the total iodine content. Thus, discussion of halogen content and release rate is based on the iodine content of the sample and the release rate of total iodine (total halogen).

[0264] The total iodine content of each sample was converted to iodine content relative to the initial iodine content ("relative iodine content") and tracked over time as described in the table below.

[0265] The total halogen release rate corresponds to the iodine release rate analyzed by the examples of the present invention.

[0266] The total halogen release rate was analyzed by tracking the relative iodine content using an exponential release rate (decay) function according to the following equation:

[0267] The formula is C_iodine / C_iodine_0 = exp(-k*time), where C_iodine is the total iodine content in each sample, C_iodine_0 is the initial total iodine content, and k is the iodine release rate (decay) constant with units of % / day. The total release rate is equal to k*C_iodine, and the relative release rate is equal to kC_iodine / C_iodine_0.

[0268] The total release rate is equal to the release rate constant (e.g., 0.5% / day) multiplied by the total halogen in the article. In other words, the release rate of the total halogen from the article is 0.5% of the total halogen in the article per day in this example. The relative release rate and the release rate constant have the same units (% / day), but differ in value depending on the relative iodine content. An exponential release rate (decay) model was used to estimate the depletion of the halogen source over time.

[0269] EDX Test

[0270] Energy dispersive X-ray spectroscopy (EDX) is an analytical technique in which an electron beam bombards a sample, resulting in an energy shift in the sample's electrons. This shift causes the sample to emit an X-ray signature. The X-ray signature allows for the identification of the elemental composition of the sample. The signal is observed in an image of the sample with light intensity reflecting the relative concentration of the target components.

[0271] Working Example

[0272] The following examples are intended to illustrate certain non-limiting embodiments of the present disclosure.

[0273] Example 1

[0274] Sorbent Polymer Composite (SPC)

[0275] SPC Material 1A. SPC containing 80% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA) and 20% PTFE was made under laboratory conditions and prepared using the general dry blending method taught in U.S. Patent No. 7,791,861 to form a composite sample. The composite sample was then uniaxially stretched according to the teachings of U.S. Patent No. 3,953,566. The thickness of SPC Material 1A was approximately 25 mils (0.635 mm).

[0276] SPC Material 1B. A composite sample was formed by preparing an SPC made under laboratory conditions containing 50% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 30% PTFE, 5% sulfur, and 15% tetrabutylammonium iodide (TBAI) using the general dry blending method taught in U.S. Pat. No. 7,791,861. The composite sample was then uniaxially stretched according to the teachings of U.S. Pat. No. 3,953,566. The thickness of SPC Material 1B was approximately 25 mils (0.635 mm).

[0277] Halogen reservoir containing SPC material

[0278] Halogen Reservoir 1A. A halogen reservoir made under laboratory conditions containing 40% activated carbon (NUCHAR SA-20, Ingevit, South Carolina, USA), 30% PTFE, 20% potassium iodide (KI) as the halogen source, and 10% iron oxide (Fe2O3) was prepared using the general dry blending method taught in U.S. Patent No. 7,791,861 to form a halogen reservoir. The thickness of halogen reservoir 1A was approximately 25-30 mils (0.635 mm-0.762 mm).

[0279] Halogen Reservoir 1B. A halogen reservoir made under laboratory conditions containing 40% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 30% PTFE, 20% potassium iodide (KI) as the halogen source, and 10% iron oxide (Fe2O3) was prepared using the general dry blending method taught in U.S. Patent No. 7,791,861 to form a halogen reservoir. The thickness of halogen reservoir 1B was approximately 25-30 mils (0.635 mm-0.762 mm).

[0280] Halogen Reservoir 1C. A halogen reservoir made under laboratory conditions containing 35% activated carbon (NUCHAR SA-20, Ingevit, SC, USA), 20% PTFE, 20% tetrabutylammonium iodide (TBAI) as the halogen source, and 25% PVDF (Hylar 301F, Solvay Specialty Polymers, LLC, Delaware, USA) was prepared using the general dry blending method taught in U.S. Patent No. 7,791,861 to form a halogen reservoir. The thickness of halogen reservoir 1C was approximately 25-30 mils (0.635 mm-0.762 mm).

[0281] Halogen Reservoir 1D. A halogen reservoir made under laboratory conditions containing 35% activated carbon (Norit PAC20BF, Cabot Inc., TX, USA), 20% PTFE, 20% tetrabutylammonium iodide (TBAI) as the halogen source, and 25% PVDF (Hylar 301F, Solvay Specialty Polymers, LLC, DE, USA) was prepared using the general dry blending method taught in U.S. Patent No. 7,791,861 to form a halogen reservoir. The thickness of the halogen reservoir 1D was approximately 25-30 mils (0.635 mm-0.762 mm).

[0282] Permeation control material in the form of an adhesive layer

[0283] Adhesive Layer 1A. A permeation control material was used in the form of an adhesive layer comprising a discontinuous PVDF NALTEX extruded network (Delstar Technologies, Inc., Delaware, USA). The thickness of adhesive layer 1A was approximately 25 mils (0.635 mm).

[0284] Adhesive Layer 1B. A permeation control material was used in the form of an adhesive layer comprising a continuous PVDF film (SOLEF PVDF 9009, Solvay Specialty Polymers, LLC, Delaware, USA). The thickness of adhesive layer 1B was 2 mil (0.05 mm).

[0285] exemplary article

[0286] ARTICLE 1A: A 5-ply SPC laminate was constructed in the following order: a) first SPC layer comprising SPC material 1A, b) first adhesive layer comprising Adhesive 1A, c) halogen reservoir layer comprising Halogen Reservoir 1A, d) second adhesive layer comprising Adhesive 1A, e) second SPC layer comprising SPC material 1A. The layers were cut into 30.5 cm x 20.3 cm (12" x 8") strips and laminated in a belt laminator at 175°C and approximately 413-620 kPa (approximately 60-90 psi) to produce the 5-ply SPC laminate, ARTICLE 1A.

[0287] ARTICLE 1B: A 5-ply SPC laminate was constructed in the following order: a) first SPC layer comprising SPC material 1A, b) first adhesive layer comprising Adhesive 1A, c) halogen reservoir layer comprising Halogen Reservoir 1B, d) second adhesive layer comprising Adhesive 1A, e) second SPC layer comprising SPC material 1A. The layers were cut into 12" x 8" strips and laminated in a belt laminator at 175°C and approximately 60-90 psi (413-620 kPa) to produce the 5-ply SPC laminate, ARTICLE 1B.

[0288] Article 1C: A three layer SPC laminate was constructed in the following order: a) a first SPC layer containing SPC material 1A, b) a halogen reservoir layer containing halogen reservoir 1C, c) a second SPC layer containing SPC material 1A. The addition of PVDF to the reservoir formulation eliminated the need for an adhesive layer. The layers were cut into 30.5 cm x 20.3 cm (12" x 8") strips and laminated in a belt laminator at 175°C and approximately 413-620 kPa (approximately 60-90 psi) to produce a three layer SPC laminate, Article 1C.

[0289] Article 1D: A three layer SPC laminate was constructed in the following order: a) a first SPC layer containing SPC material 1A, b) a halogen reservoir layer containing halogen reservoir 1D, c) a second SPC layer containing SPC material 1A. The addition of PVDF to the reservoir formulation eliminated the need for an adhesive layer. The layers were cut into 30.5 cm x 20.3 cm (12" x 8") strips and laminated in a belt laminator at 175°C and approximately 413-620 kPa (approximately 60-90 psi) to produce the three layer SPC laminate, Article 1D.

[0290] Combustion exhaust gas flow durability test. Articles 1C and 1D were loaded into the above-mentioned combustion exhaust gas durability test, and the total iodine content was measured over time. The total iodine content was converted to the iodine content relative to the initial iodine content as shown in Table 1.

[0291] The release rate constant (iodine content decay constant k) was 1.3% / day for Article 1C and 0.22% / day for Article 1D.

[0292] [Table 1]

[0293] Using an exponential release rate model (shown in FIG. 6A by the respective dashed lines), extrapolation of the flue gas stream durability data showed that Article 1C exhibited 90% depletion (shown by horizontal line L) in less than 200 days. In some embodiments, the activated carbon can be selected to adjust the release rate of iodine from the reservoir. For example, Article 1D, which utilizes a different type of activated carbon than Article 1C, exhibited significantly enhanced durability, exhibiting 90% depletion in about 1000 days. FIG. 6A shows the relative iodine content over time for Article 1C (a 3-ply SPC laminate) and Article 1D (a 3-ply SPC laminate).

[0294] Articles 1A and 1B were loaded into the flue gas durability test and the relative iodine content was tracked over time, as shown in Table 2. The release rate constant (iodine content decay constant k) was 0.63% / day for Article 1A and 0.30% / day for Article 1B.

[0295] [Table 2]

[0296] 6B shows the relative iodine content over time for Article 1A and Article 1B (both 5-ply SPC laminates). For Article 1A, 90% depletion was estimated at approximately 400 days. Article 1B, utilizing a different type of activated carbon than Article 1A, showed significantly enhanced durability with 90% depletion estimated at approximately 800 days (shown by horizontal line L). In some embodiments, the activated carbon can be selected to adjust the release rate of iodine from the reservoir.

[0297] Example 2

[0298] Halogen reservoir samples with and without (comparative) permeation control layer

[0299] Halogen Reservoir 2A without Permeation Control Layer: Iodine loaded polymer was prepared by exposing a 2.5 cm x 8.1 cm and 0.79 mm thick polystyrene (PS) sheet (part number 8734K31, McMasterCarr Supply Co., IL, USA) with excess iodine (I) in a closed container at 90°C for a period of 48 hours, resulting in an iodine loading of approximately 40% by weight.

[0300] Halogen Reservoir 2B with Permeation Control Layer. Halogen reservoir 2A was applied using a two-component epoxy (part number 66195A13, McMasterCarr Supply Co., IL, USA) to cover all surfaces of the reservoir, thereby forming a three-layer reservoir.

[0301] Halogen Reservoir 2C without Permeation Control Layer: Iodine loaded polymer was prepared by exposing a 1.0 cm x 6.0 cm and 0.79 mm thick polystyrene (PS) sheet (part number 8734K31, McMasterCarr Supply Co., IL, USA) with excess iodine (I) in a closed container at 80°C for a period of 16 hours, resulting in an iodine loading of approximately 20% by weight.

[0302] Halogen Reservoir 2D with Permeation Control Layer: Halogen reservoir 2C was laminated between two or more 1 mil (0.025 mm) thick PVDF films (permeation control layers) (SOLEF PVDF 9009, Solvay Specialty Polymers, LLC, Delaware, USA) on a belt laminator using 248-276 kPa (36-40 psi) gauge pressure and 175°C, thereby forming a 3-layered or 4-layered or more halogen reservoir.

[0303] The halogen reservoir 2D was manufactured in different embodiments. a) Halogen reservoir 2D(4): Four permeation control layers were laminated onto each surface of the halogen reservoir 2C. b) Halogen reservoir 2D(5): Five permeation control layers were laminated onto each surface of the halogen reservoir 2C. c) Halogen reservoir 2D(6): Six permeation control layers were laminated onto each surface of the halogen reservoir 2C. d) Halogen reservoir 2D(8): Eight permeation control layers were laminated onto each surface of the halogen reservoir 2C.

[0304] Iodine Stability Test

[0305] The stability of halogen reservoirs 2A and 2B was tested by exposing the samples to heat inside a 60°C oven for approximately 1000 hours. Halogen reservoirs 2A and 2B were each placed in a vial and then closed with a cap. The vials also contained activated charcoal to capture lost iodine. The total iodine content (wt%) of halogen reservoirs 2A and 2B was determined over time during the test by gravimetry and normalized to the halogen reservoir alone (sample 2A) without the permeation control layer. Halogen reservoir 2B exhibited significantly slower iodine release due to the barrier formed by the permeation control layer consisting of crosslinked epoxy. The comparative iodine release rates are summarized in Figure 7A.

[0306] The stability of halogen reservoirs 2C and 2D was tested by exposing the samples to heat inside a 60° C. oven for over about 1200 hours. Halogen reservoirs 2C and 2D were each placed in a vial and then closed with a cap. The vials also contained activated charcoal to capture lost iodine. The total iodine content (wt%) of halogen reservoirs 2C and 2D was determined over time during the test by gravimetry and normalized to the halogen reservoir only (sample 2C) without a permeation control layer. Halogen reservoir 2D exhibited significantly slower iodine release compared to halogen reservoir 2C due to the barrier formed by the permeation control layer consisting of PVDF layers. The comparative iodine release rates were affected by the number of PVDF permeation control layers and are summarized in FIG. 7B. As shown in FIG. 7B, the halogen release rate can vary as a function of the number of permeation control layers. Specifically, the halogen reservoirs 2C and 2D were tested with 0-8 permeation control material layers in the form of PVDF films on each side of the halogen reservoir to characterize the release rate characteristics of the at least one permeation control material. Even though 2C appears inherently better than 2D, the performance of 2D can be improved over that of 2C by adding more permeation control layers.

[0307] Example 3

[0308] SPC laminates containing halogen reservoir layers containing iodine loaded carbon

[0309] Iodine-loaded carbon 3A. Iodine on carbon was prepared by mixing 100 grams of iodine (I) with 300 grams of activated carbon (Norit PAC20BF, Cabot Inc., TX, USA). The mixture was heated to 60°C in a sealed glass container for 4-6 hours. The resulting iodine loading of the activated carbon was approximately 25% by weight.

[0310] Halogen Reservoir Solution

[0311] Halogen Reservoir Solution 3A. Two grams of iodine loaded carbon 3A was added to 25 ml of a solution of 4 wt % PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent, and 10 ml of additional THF solvent was added to reduce the viscosity, resulting in a 2:1 I2-carbon:PVDF ratio.

[0312] Halogen Reservoir Solution 3B. 2.4 grams of iodine loaded carbon 3A was added to 23 mL of a solution of 16 wt % PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent, and 10 mL of additional THF solvent was added to reduce the viscosity, resulting in an I2-carbon:PVDF ratio of 1:1.5.

[0313] Halogen reservoir solution 3C. A 16 wt% solution of PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent was mixed with enough iodine-loaded carbon 3A to give a I2-carbon:PVDF ratio of 1:1.5.

[0314] Halogen reservoir solution 3D. A 21 wt% solution of PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent was mixed with enough iodine-loaded carbon 3A to give a I2-carbon:PVDF ratio of 1:1.5.

[0315] Halogen reservoir solution 3E. A 16 wt % solution of PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent was mixed with enough iodine-loaded carbon 3A to give an I2-carbon:PVDF ratio of 1:1.25.

[0316] Halogen reservoir solution 3F. A 20 wt % solution of PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent was mixed with enough iodine-loaded carbon 3A to give a 1:1 I2-carbon:PVDF ratio.

[0317] Permeability control material solution

[0318] Permeation control material solution 3A. A solution of 18 wt % PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent was prepared.

[0319] Permeation control material solution 3B. A solution of 20 wt % PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent was prepared.

[0320] Sorbent Polymer Composite (SPC) (without halogen source)

[0321] Sorbent Polymer Composite (SPC) Material 3A. A sorbent polymer composite consisting of 80 parts activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA) and 20 parts PTFE was made under laboratory conditions and prepared using the general dry blending method taught in U.S. Pat. No. 7,791,861 to form SPC material 3A.

[0322] Sorbent Polymer Composite (SPC) Material 3B. A sorbent polymer composite containing 75 parts activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA) and 25 parts PTFE was made under laboratory conditions and prepared using the general dry blending method taught in U.S. Pat. No. 7,791,861, and then uniaxially stretched according to the teachings of U.S. Pat. No. 3,953,566 to form SPC material 3B.

[0323] exemplary article

[0324] Article 3A: Using an airbrush (Master E91 Airbrush, TCP Global Corp., CA, USA), Halogen Reservoir Solution 3A was applied onto the surface of several 1.25" x 12" (3.175 cm x 30.48 cm) SPC material strips at approximately 138 kPa (20 psi) gauge pressure. The SPC material strip thickness was 0.617 mm before coating and 0.907 mm after coating and drying (average based on eight SPC strips), representing a thickness gain of 0.290 mm. The average weight of the coating added was 1.37 grams. The coated sides of the coated and dried SPC material strip pairs were mated and laminated on a belt laminator using 248-276 kPa (36-40 psi) gauge pressure and 180°C to form an SPC laminate. Four laminates were prepared for durability testing. The initial total iodine content of these prototypes was determined by X-ray fluorescence (XRF) analysis to be 3.29 wt%.

[0325] Article 3B: Using an airbrush (Master E91 Airbrush, TCP Global Corp., CA, USA), Halogen Reservoir Solution 3B was applied onto the surface of several 1.25" x 12" (3.175 cm x 30.48 cm) SPC material strips at approximately 138 kPa (20 psi) gauge pressure. The SPC material strip thickness was 0.617 mm before coating and 0.944 mm after coating and drying (average based on eight SPC strips), indicating a thickness gain of 0.327 mm. The average weight of the coating added was 1.38 grams. The coated sides of the coated and dried SPC material strip pairs were mated and laminated on a belt laminator using 248-276 kPa (36-40 psi) gauge pressure and 180°C to form an SPC laminate. Four laminates were prepared for durability testing. The initial total iodine content of these prototypes was determined by X-ray fluorescence (XRF) analysis to be 4.14 wt%.

[0326] Flue Gas Stream Durability Test. During the flue gas stream durability test, Articles 3A and 3B were suspended and the relative iodine concentration was tracked over time as described in Table 3. The halogen release rate constant (iodine content decay constant k) was 0.65% / day for Article 3A and 0.13% / day for Article 3B.

[0327] [Table 3]

[0328] Figure 8A shows the relative iodine content of Articles 3A and 3B versus time as set forth in Table 3. Using an exponential release rate (decay) model, also shown in Figure 8A by the respective dashed lines, extrapolating the flue gas stream durability data, Article 3A exhibited less than one year of iodine release before approaching 90% depletion (indicated by horizontal line L), and Article 3B exhibited more than three years of iodine release before approaching 90% depletion.

[0329] Article 3C: Halogen reservoir solution 3C was applied to the surface of a 4 inch (10.16 cm) wide roll of SPC material 3B using roll-to-roll application. The solution was charged to a mixing tank and then applied to the SPC material using a coating head with a 15 mil (0.381 mm) gap. The coated wet SPC layer was passed through a 104°C oven for approximately 15 minutes, allowed to dry in place, and then collected on a take-up roll. Two dried SPC layers were mated and laminated on a belt laminator using 248-276 kPa (36-40 psi) gauge pressure and 150°C. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain an initial total iodine content of approximately 0.218 wt%.

[0330] Article 3D: Halogen reservoir solution 3D was applied to the surface of a 4 inch (10.16 cm) wide roll of SPC material 3B using roll-to-roll coating. The solution was charged to a mixing tank and then applied to the SPC material using a coating head with a 20 mil (0.508 mm) gap. The coated wet SPC layer was passed through a 104°C oven for approximately 20 minutes, allowed to dry in place, and then collected on a take-up roll. Two dried SPC layers were mated and laminated on a belt laminator using 248-276 kPa (36-40 psi) gauge pressure and 150°C. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain an initial total iodine content of approximately 0.245 wt%.

[0331] Article 3E: Halogen reservoir solution 3C was applied to the surface of a 4 inch (10.16 cm) wide roll of SPC material 3B using roll-to-roll application. The solution was charged to a mixing tank and then applied to the SPC material using a coating head with a 50 mil (1.27 mm) gap. The coated wet SPC layer was passed through a 104°C oven for approximately 30 minutes, allowed to dry in place, and then collected on a take-up roll. The two dried SPC layers were mated and laminated on a belt laminator using 248-276 kPa (36-40 psi) gauge pressure and 150°C. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain an initial total iodine content of approximately 0.310 wt%.

[0332] Article 3F: Halogen Reservoir Solution 3A was applied as a first coat to the surface of a 4 inch (10.16 cm) wide roll of SPC material 3B using roll-to-roll coating. The solution was charged to a mixing tank and then applied to the SPC material using a coating head with a 10 mil (0.254 cm) gap. The coated wet SPC layer was passed through a 104° C. oven for approximately 7 minutes, dried in place and then collected on a take-up roll. A second coat of Halogen Reservoir Solution 3E was applied to the surface of the dried permeation control material layer using roll-to-roll coating. The solution was charged to a mixing tank and then applied to the dried permeation control material layer of SPC material 3B using a coating head with a 40 mil (1.016 mm) gap. The coated wet SPC layer was passed through a 104° C. oven for approximately 7 minutes, dried in place and then collected on a take-up roll. The two dried SPC layers were mated and laminated on a belt laminator using 248-276 kPa (36-40 psi) gauge pressure and 150° C. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain an initial total iodine content of approximately 1.15 wt%.

[0333] Article 3G: Permeation control material solution 3B was applied as a first coat to a 4 inch (10.16 cm) wide surface of SPC material 3B using a casting knife film applicator. A coating head with a 10 mil (0.254 cm) gap was used to apply the solution to the SPC material. A second coat of halogen reservoir solution 3F was applied to the surface of the dried permeation control material layer of SPC material 3B using a casting knife film applicator. A coating head with a 40 mil (1.016 cm) gap was used to apply the solution to the SPC material. The applied wet SPC layer was allowed to dry overnight at room temperature. The two dried SPC layers were mated and laminated on a belt laminator using 248-276 kPa (36-40 psi) gauge pressure and 150°C. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain an initial total iodine content of approximately 4.85 wt%.

[0334] Combustion exhaust gas flow durability test

[0335] Articles 3C-3G were tested in a flue gas stream durability test and the relative iodine content was tracked over time as described in Table 4. The halogen release rate constants (iodine content decay constant k) were 0.39% / day for Article 3C, 0.01% / day for Article 3D, 0.17% / day for Article 3E, 0.00% / day for Article 3F, and 0.03% / day for Article 3G. FIG. 8B shows the relative iodine content of Articles 3C-3G versus time. Using the exponential release rate (decay) model also shown in FIG. 8B by the respective dashed lines, extrapolation of the flue gas stream durability data indicates that Article 3C exhibited approximately 2 years of iodine release before approaching 90% depletion (shown by horizontal line L). Articles 3D, 3E, 3F, and 3G release boron for longer periods of time.

[0336] [Table 4]

[0337] EDX Test

[0338] The cross section 600 of the article 3B after 101 days of field exposure was analyzed according to EDX test (energy dispersive X-ray analysis). The EDX test maps the iodine (halogen) content of the cross section of the article 3B, and shows that the halogen reservoir layer 601 was still intact, as shown by the high light intensity in the center of the cross section, and that iodine was released into the SPC layer 602, as shown by the scattered dots in the SPC layer 602, as shown in FIG. 8C. The same cross section of the article 3B after 101 days of field exposure was analyzed according to EDX test (energy dispersive X-ray analysis) to show the sulfur content. FIG. 8D shows that the SPC layer 620 is highly effective as a barrier against SO2 and sulfuric acid, as shown by the bright intensity in the halogen reservoir layer 602 and the low light intensity in the halogen reservoir layer 601.

[0339] The same cross section 600 of Article 3G after 31 days of field exposure was analyzed according to EDX test analysis for iodine (halogen) content. Figure 8E shows that the halogen reservoir layer 601 was intact as indicated by the light intensity at the center of the cross section, and that the iodine (halogen) had been released into the SPC layer 602 as indicated by the dispersed dots in the SPC layer 602 of the sample.

[0340] Example 4 (SPC layer without halogen source)

[0341] Sorbent Polymer Composite (SPC)

[0342] SPC Material 4A. SPC containing 75% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA) and 25% PTFE was made under laboratory conditions and prepared using the general dry blending method taught in U.S. Patent No. 7,791,861 to form composite samples. The composite samples were then uniaxially stretched according to the teachings of U.S. Patent No. 3,953,566.

[0343] SPC Material 4B. An SPC containing 72% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 22% PTFE, and 6% sulfur was made under laboratory conditions and a composite sample was formed by preparing the SPC using the general dry blending method taught in U.S. Pat. No. 7,791,861.

[0344] Halogen Reservoir Layer Components

[0345] The halogen reservoir layer in the following examples is comprised of an iodide salt (halogen source) mixed with a polyolefin (permeation control material) and includes the following components: Iodide Salt 4A: Tetrabutylammonium Iodide (TBAI), Iodide Salt 4B: Ethyltriphenylphosphonium Iodide (ETPPI3), Hot Melt Adhesive 4A (RT6825 from REXTac LLC, Texas, USA), Hot Melt Adhesive 4B (RT2535 from REXTac LLC, Texas, USA).

[0346] ARTICLE 4A (3-ply SPC laminate). A layer of SPC material 4A was cut into 14 cm x 30 cm pieces. The piece of SPC material 4A was run through a roll coater (Model HOT COATTM 16 manufactured by Glue Machinery Corporation, Maine, USA). The coater was filled with a permeation control material in the form of hot melt adhesive 4A. A coating head with a 15 mil (0.381 mm) gap was used to apply the hot melt adhesive 4A to a layer of SPC material 4A. The bath setting was 350°F (176.6°C) and the roll temperature setting was 220°F (104.4°C). The SPC layer 4A was then laid flat with the hot melt adhesive 4A facing up. 1.5 g of iodide salt 4A (TBAI) was then sprinkled onto the hot melt adhesive, thereby forming an SPC layer with a wet applied halogen reservoir layer. Before the permeation control material in the form of a hot melt adhesive solidified, two pieces of SPC layer 4A with wet applied halogen reservoir layers were mated by facing the halogen reservoir layers to sandwich the iodide salt 4A (TBAI) between the two polyolefin permeation control material layers, forming an article 4A consisting of a three layer SPC laminate with a halogen reservoir consisting of a polyolefin permeation control material as an intermediate layer and TBAI as the halogen source.

[0347] Comparative Article 4AA. A layer of SPC material 4A was cut into 14 cm x 30 cm pieces. The pieces of SPC material 4A were run through a roll coater (Model HOT COATTM 16, manufactured by Glue Machinery Corporation, Maine, USA). The coater was filled with hot melt adhesive 4A. A coating head with a 15 mil (0.381 mm) gap was used to apply the hot melt adhesive 4A to a layer of SPC material 4A. The bath setting was 350°F (176.6°C) and the roll temperature setting was 220°F (104.4°C) to form an SPC layer with a wet applied reservoir layer. Two pieces of SPC layer 4A with wet applied halogen reservoir layers were mated by facing the polyolefin permeation control layers, thereby forming Article 4AA as a three layer SPC laminate.

[0348] Comparative Article 4BB. A permeation control material in the form of hot melt adhesive 4B (RT2535, REXTac LLC, Texas, USA) was melted in an aluminum pan on top of a first hot plate. The temperature setting on the hot plate knob was 200°C. The SPC material 4B layer was cut into a 14 cm x 30 cm piece. The first SPC material 4B piece was placed on a second hot plate (the hot plate temperature was approximately 108°C as measured with an IR thermometer). The thickness of the first SPC piece was 0.63 mm. The edges of the first SPC piece were covered with aluminum foil by approximately 2 cm on each side, leaving approximately 10 cm x 30 cm exposed. A portion of hot melt adhesive 4B was poured on top of the first SPC piece and spread using a metal spatula. Before the hot melt adhesive solidified, a second SPC material piece 4B with a thickness of 0.62 mm was placed on top and gently pressed by hand and spatula until a bond was formed. The total thickness of Article 4BB was 1.508 mm. The average thickness of the permeation control layer was estimated to be 0.256 mm by subtracting the thickness of SPC material 4B from the thickness of Article 4BB.

[0349] Article 4B. Article 4B was prepared according to the procedure described for Article 4BB. A permeation control material in the form of hot melt adhesive 4B was melted on top of a first hot plate (temperature setpoint approximately 220°C). A piece of the first SPC material 4B with size 14 x 30 cm and thickness 0.62-0.63 mm was placed on a second hot plate with a temperature of approximately 120°C. The sample was prepared using the procedure described for Article 4BB, but before pouring the hot melt adhesive 4B on the second SPC material 4B piece, a predetermined amount of iodide salt 4B (ETPPI) was mixed with the hot melt adhesive 4B using a glass stirring rod. The average content of ETPPI in the hot melt adhesive 4B was approximately 30% by weight. Before the hot melt adhesive solidified, the second SPC material piece 4B was placed on top and gently pressed by hand and spatula until a bond was formed. The total thickness of Article 4B was approximately 1.8 mm. The average thickness of the hot melt adhesive layer was approximately 0.47 mm, estimated by subtracting the thickness of the two SPC materials 4B from the thickness of Article 4B. This formed a three-layer SPC laminate (Article B) having two SPC layers (SPC material 4B) and a halogen reservoir between the two SPC layers formed from a permeation control material (hot melt adhesive 4B) mixed with a halogen source (iodide salt) 4B.

[0350] Samples of SPC laminates having a halogen reservoir layer formed from polyolefin RT2535 with and without a halogen source in the form of TBAI iodide salt were prepared using the following procedure.

[0351] Article 4C. Article 4C was prepared according to the procedure described for Article 4BB. A permeation control material in the form of hot melt adhesive 4B was melted on top of a first hot plate (temperature setting of approximately 220°C). A piece of the first SPC material 4B with size 14 x 30 cm was placed on a second hot plate with a temperature of approximately 120°C. The sample was prepared using the procedure described for Article 4BB, but before pouring the hot melt adhesive 4B on the second SPC material 4B piece, a predetermined amount of iodide salt 4B (ETPPI) was mixed with the hot melt adhesive 4B using a glass stirring rod. The average content of TBAI in the polyolefin was about 22 wt%. Before the hot melt adhesive solidified, the second SPC material piece 4B was placed on top and gently pressed by hand and spatula until a bond was formed. The total thickness of Article 4C was approximately 1.85 mm. The average thickness of the hot melt adhesive layer was about 0.5-0.6 mm, estimated by subtracting the thickness of the two SPC materials 4B from the thickness of the article 4C.

[0352] This formed a three-layer SPC laminate (article 4C) having two SPC layers (SPC material 4B) and a halogen reservoir between the two SPC layers formed from a permeation control material (hot melt adhesive 4B) mixed with a halogen source (iodide salt) 4A.

[0353] Combustion exhaust gas flow durability test

[0354] Articles 4A and 4B were loaded into the flue gas durability test along with Articles 4AA and 4BB, and the iodine content was measured over time as described in Table 5. The iodine release rate constant was 0.94% / day for Article 4A and 0.38% / day for Article 4B. FIG. 9 shows the relative iodine content of Articles 4A and 4B. Using an exponential release rate (decay) model, also shown in FIG. 9 by the respective dashed lines, extrapolating the flue gas stream durability data, Article 4A had an iodine release of less than 300 hours before approaching 90% depletion (shown by horizontal line L). Article 4B had an iodine release of approximately 600 hours before approaching 90% depletion.

[0355] [Table 5]

[0356] Strips of Article 4AA were collected after 75 and 197 days of exposure. Their total iodine contents were 0.006 wt% and 0.07 wt%, respectively. Strips of Article 4BB were collected after 71 and 191 days of exposure. Their total iodine contents were 0.003 wt% and 0.03 wt%, respectively. The low levels of total iodine content for Articles 4AA and 4BB indicate that there was not a significant source of iodine in the flue gas stream that could have deposited in the samples; that is, Articles 4AA and 4BB did not acquire any iodine.

[0357] Simulated combustion exhaust gas flow durability test

[0358] Articles 4B and 4C were loaded into a simulated laboratory durability test and the iodine content was measured over time as described in Table 6. Articles 4B (average of two samples) and 4C (average of two samples) did not lose any iodine over the entire test period. The release rate constant (iodine content decay constant k) is approximately zero.

[0359] [Table 6]

[0360] Comparative Example

[0361] SPC Comparative Sample 5A. A sorbent polymer composite (SPC) consisting of 40% activated carbon (NUCHAR SA-20, Ingevit, South Carolina, USA), 50% PTFE, 3% potassium iodide (KI) as a halogen source, and 7% sulfur was prepared under laboratory conditions and the composite sample was formed by preparing the sorbent polymer composite (SPC) using the general dry blending method taught in U.S. Patent No. 7,791,861. The composite sample was then uniaxially stretched according to the teachings of U.S. Patent No. 3,953,566.

[0362] SPC Comparative Sample 5B. A sorbent polymer composite (SPC) consisting of 50% activated carbon (NUCHAR SA-20, Ingevit, South Carolina, USA), 39% PTFE, 6% tetrabutylammonium iodide (TBAI) as a halogen source, and 5% sulfur was prepared under laboratory conditions and the composite sample was formed by preparing the sorbent polymer composite (SPC) using the general dry blending method taught in U.S. Patent No. 7,791,861. The composite sample was then uniaxially stretched according to the teachings of U.S. Patent No. 3,953,566.

[0363] Simulated combustion exhaust gas flow durability test

[0364] SPC Comparative Samples 5A and 5B were loaded into flue gas stream durability testing and the relative iodine content was tracked over time as described in Table 7. The halogen release rate constant (iodine content decay constant k) was determined to be 17.7% / day for SPC Comparative Sample 5A and 16.3% / day for SPC Comparative Sample 5B. The relative iodine content of Comparative Samples 5A and 5B is shown in FIG. 10, which shows the relative iodine content measured over a 14 day period. Using an exponential release rate (decay) model, also shown in FIG. 10 by the respective dashed lines, extrapolating the flue gas stream durability data, SPC Comparative Samples 5A and 5B exhibited only about 15 days of iodine release before approaching 90% depletion (shown by horizontal line L).

[0365] [Table 7]

[0366] Flue Gas Stream Durability Testing. SPC Comparative Samples 5A and 5B were loaded during the flue gas stream durability test. The relative iodine content was tracked over time as described in Table 8. The halogen release rate constant (iodine content decay constant k) was determined to be 15% / day for SPC Comparative Sample 5A and 9.0% / day for SPC Comparative Sample 5B. As shown in Table 8 and FIG. 11, Comparative Samples 5A and 5B reach 90% iodine depletion (indicated by horizontal line L) in less than 10 days. The relative iodine content in FIG. 11 was measured over 24 and 51 days, respectively.

[0367] [Table 8]

[0368] Aspects

[0369] Various embodiments are described below. It should be understood that any one or more of the features listed in the embodiments below may be combined with any one or more of the other embodiments. Aspect 1 a first sorbent polymer composite (SPC) layer; A second SPC layer; Halogen Reservoir and An article comprising: the halogen reservoir is disposed between the first SPC layer and the second SPC layer; Goods. Aspect 2 The article of embodiment 1, further comprising at least one permeation control material. Aspect 3 the at least one permeation control material is in the form of at least one permeation control layer; The at least one transmission control layer is Between the first SPC layer and the halogen reservoir, between the second SPC layer and the halogen reservoir; or Located on both An article according to any one or combination of the preceding and following aspects. Aspect 4 The at least one transmission control layer is The first layer of at least one permeation control material, a first layer, the first layer being disposed between the first SPC layer and the halogen reservoir; A second layer of the at least one permeation control material, a second layer, the second layer being disposed between the second SPC layer and the halogen reservoir; An article according to any one or combination of the preceding and following aspects. Aspect 5 The article according to any one or combination of the preceding and following aspects, wherein the halogen reservoir comprises at least one halogen source. Aspect 6 The article according to any one or combination of the preceding and following aspects, wherein the at least one halogen source comprises at least one halide ion or elemental halogen. Aspect 7 13. The article according to any one or combination of the preceding and following aspects, wherein the halogen reservoir comprises 0.1 wt.% to 50 wt.% of at least one halogen source, based on a total weight of the halogen reservoir. Aspect 8 The article according to any one or combination of the preceding or following aspects, wherein the halogen reservoir comprises SPC. Aspect 9 The article according to any one or combination of the preceding or following aspects, wherein the halogen reservoir comprises a third SPC layer. Aspect 10 The article according to any one or combination of the preceding and following aspects, wherein at least one of the first SPC layer, the second SPC layer, or the third SPC layer comprises at least one halogen source. Aspect 11 The article according to any one or combination of the preceding and following aspects, wherein the halogen reservoir comprises at least one permeation control material. Aspect 12 The halogen reservoir comprises: 5 wt% to 95 wt% of at least one permeation control material based on the total weight of the halogen reservoir; 5 wt% to 50 wt% of at least one halogen source based on the total weight of the halogen reservoir; An article according to any one or combination of the preceding and following aspects. Aspect 13 The at least one permeation control material is A first permeability control material; A second permeability control material; Including, the second permeation control material is in the form of at least one layer of the second permeation control material; At least one layer of the second permeation control material is Between the first SPC layer and the halogen reservoir, between the second SPC layer and the halogen reservoir; or between the first SPC layer and the halogen reservoir, and between the second SPC layer and the halogen reservoir. Located, An article according to any one or combination of the preceding and following aspects. Aspect 14 At least one layer of the second permeation control material is A first layer made of the second permeation control material, a first layer of the second permeation control material disposed between the first SPC layer and the halogen reservoir; A second layer made of the second permeation control material, a second layer of the second permeation control material disposed between the second SPC layer and the halogen reservoir; An article according to any one or combination of the preceding and following aspects. Aspect 15 The article according to any one or combination of the preceding or subsequent aspects, wherein the halogen reservoir further comprises carbon particles. Aspect 16 The article according to any one or combination of the preceding and following aspects, wherein the carbon particles are embedded within the at least one permeation control material. Aspect 17 said article having a release rate of total halogens from said article that does not exceed 0.5% of the total halogens in said article per day when a flue gas stream is caused to flow over at least one surface of said article for a period of at least 90 days; The flue gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%, and the flue gas stream contains at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of An article according to any one or combination of the preceding and following aspects. Aspect 18 said article having a release rate of total halogens from said article that does not exceed 2% of the total halogens in said article per day when a flue gas stream is caused to flow over at least one surface of said article for a period of at least 90 days; The flue gas stream has a temperature of at least 20° C. and a relative humidity of at least 95%, and the flue gas stream contains at least one SO 2 species at a concentration of at least 1 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of An article according to any one or combination of the preceding and following aspects. Aspect 19 13. An article according to any one or combination of the preceding and following aspects, wherein the article comprises a filter laminate, a layered filter material, an SPC laminate, or a layered SPC material. Aspect 20 1. A method of forming an article, comprising: Obtaining a first sorbent polymer composite (SPC) layer; Obtain a second SPC layer, Obtaining a halogen reservoir; disposing the halogen reservoir between the first and second SPC layers to produce a layered structure; and The layered structure is attached together to form the article. An article according to any one or combination of the preceding and following aspects. Aspect 21 disposing the halogen reservoir between the first and second SPC layers; such that the formed article includes at least one permeation control layer. disposing at least one permeation control layer between the first SPC layer and the halogen reservoir; disposing the at least one permeation control layer between the second SPC layer and the halogen reservoir; or Do both An article according to any one or combination of the preceding and following aspects. Aspect 22. The method of claim 22, further comprising disposing the halogen reservoir between the first and second SPC layers. disposing a first layer of at least one permeation control material between the first SPC layer and the halogen reservoir; and A second layer of at least one permeation control material is disposed between the second SPC layer and the halogen reservoir. An article according to any one or combination of the preceding and following aspects. Aspect 23 further comprising combining at least one halogen source with at least one permeation control material to form the halogen reservoir; The halogen reservoir comprises: said at least one halogen source; said at least one permeation control material; An article according to any one or combination of the preceding and following aspects. Aspect 24 Combining the at least one halogen source with the at least one permeation control material comprises: heating the at least one permeation control material to a temperature sufficient to melt the at least one permeation control material; and Mixing the at least one molten permeation control material with at least one halogen source. An article according to any one or combination of the preceding and following aspects. Aspect 25 The article according to any one or combination of the preceding and following aspects, wherein the temperature sufficient to melt the at least one permeation control material is between 130°C and 180°C. Aspect 26 Combining the at least one halogen source with the at least one permeation control material comprises: forming a mixture by dissolving the at least one permeation control material in a solvent; adding at least one halogen source to the mixture of the solvent and the at least one permeation control material; and The solvent is evaporated. An article according to any one or combination of the preceding and following aspects. Aspect 27 The article according to any one or combination of the preceding and subsequent aspects, further comprising adding particles to the mixture of the at least one halogen source, solvent, and the at least one permeation control material. Aspect 28 The article according to any one or combination of the preceding or following aspects, wherein the particles are carbon particles. Aspect 29 Combining the at least one halogen source with the at least one permeation control material comprises: forming a chemical complex having said at least one halogen source and said at least one permeation control material; An article according to any one or combination of the preceding and following aspects. Aspect 30 The article according to any one or combination of the preceding and following aspects, wherein the at least one halogen source is a solution. Aspect 31 The article according to any one or combination of the preceding and following aspects, wherein the at least one halogen source is in a gas phase. Aspect 32 The article according to any one or combination of the preceding and following aspects, wherein the at least one halogen source is a salt. Aspect 33 further comprising flowing a flue gas stream over at least one surface of the article for a period of at least 90 days; the flue gas stream having a temperature of at least 50° C. and a relative humidity of at least 95%; the flue gas stream comprising: At least one SO at a concentration of at least 20 ppm x A compound, at least 1 μg / m based on the total volume of the flue gas stream 3 with a concentration of mercury vapor Including, During flow of the flue gas stream, the release rate of the total halogens in the article does not exceed 0.5% of the total halogens in the article per day; An article according to any one or combination of the preceding and following aspects. Aspect 34 further comprising flowing a flue gas stream over at least one surface of the article for a period of at least 90 days; the flue gas stream having a temperature of at least 20° C. and a relative humidity of at least 95%; the flue gas stream comprising: At least one SO at a concentration of at least 1 ppm x A compound, at least 1 μg / m based on the total volume of the flue gas stream 3 with a concentration of mercury vapor Including, During flow of the flue gas stream, the release rate of the total halogens in the article does not exceed 2% of the total halogens in the article per day; An article according to any one or combination of the preceding and following aspects.

[0370] It should be understood that changes may be made in details, particularly in materials of construction employed, and in the shape, size and arrangement of parts without departing from the scope of the present disclosure. The specification and described embodiments are by way of example only, with the true scope and spirit of the disclosure being indicated by the following claims.

Claims

1. a first sorbent polymer composite (SPC) layer; A second SPC layer; and a halogen reservoir; At least one permeation control material; A decontamination article comprising: the halogen reservoir is disposed between the first SPC layer and the second SPC layer; Goods.

2. the at least one permeation control material is in the form of at least one permeation control layer; The at least one transmission control layer comprises: Between the first SPC layer and the halogen reservoir, between the second SPC layer and the halogen reservoir, or Located on both The article of claim 1.

3. The at least one transmission control layer comprises: The first layer of at least one permeation control material, a first layer, the first layer being disposed between the first SPC layer and the halogen reservoir; A second layer of the at least one permeation control material, a second layer, the second layer being disposed between the second SPC layer and the halogen reservoir; The article of claim 2 comprising:

4. 4. The article of any one of claims 1 to 3, wherein the halogen reservoir comprises at least one halogen source.

5. 5. The article of claim 4, wherein the at least one halogen source comprises at least one halide ion or elemental halogen.

6. 5. The article of claim 4, wherein the halogen reservoir comprises from 0.1 wt % to 50 wt % of the at least one halogen source, based on a total weight of the halogen reservoir.

7. The article of any one of claims 1 to 6, wherein the halogen reservoir comprises SPC.

8. The article of claim 1 , wherein the halogen reservoir comprises a third SPC layer.

9. 9. The article of claim 8, wherein at least one of the first SPC layer, the second SPC layer, or the third SPC layer comprises at least one halogen source.

10. The article of claim 1 , wherein the halogen reservoir comprises at least one permeation control material.

11. The halogen reservoir comprises: 5 wt % to 95 wt % of the at least one permeation control material, based on the total weight of the halogen reservoir; 5 wt % to 50 wt % of at least one halogen source, based on the total weight of the halogen reservoir; The article of claim 10 comprising:

12. The at least one permeation control material is A first permeation control material; A second permeability control material; Including, the second permeation control material is in the form of at least one layer of the second permeation control material; The at least one layer of the second permeation control material is Between the first SPC layer and the halogen reservoir, between the second SPC layer and the halogen reservoir, or Between the first SPC layer and the halogen reservoir, and between the second SPC layer and the halogen reservoir. Located, 11. The article of claim 1 or 10.

13. The at least one layer of the second permeation control material is A first layer made of the second permeation control material, a first layer of the second permeation control material disposed between the first SPC layer and the halogen reservoir; A second layer made of the second permeation control material, a second layer of the second permeation control material disposed between the second SPC layer and the halogen reservoir; The article of claim 12 comprising:

14. The article of claim 10 , wherein the halogen reservoir further comprises carbon particles.

15. 15. The article of claim 14, wherein the carbon particles are embedded within the at least one permeation control material.

16. said article having a release rate of total halogens from said article that does not exceed 0.5% of the total halogens in said article per day when a flue gas stream is caused to flow over at least one surface of said article for a period of at least 90 days; The flue gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%, and the flue gas stream contains at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of 16. The article of any one of claims 1 to 15.

17. said article having a release rate of total halogens from said article that does not exceed 2% of the total halogens in said article per day when a flue gas stream is caused to flow over at least one surface of said article for a period of at least 90 days; The flue gas stream has a temperature of at least 20° C. and a relative humidity of at least 95%, and the flue gas stream contains at least one SO 2 species at a concentration of at least 1 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of 16. The article of any one of claims 1 to 15.

18. 18. The article of any one of claims 1 to 17, wherein the article comprises a filter laminate, a layered filter material, an SPC laminate, or a layered SPC material.

19. A method of forming an article for decontamination, comprising the steps of: Obtaining a first sorbent polymer composite (SPC) layer; Obtaining a second SPC layer; Obtaining a halogen reservoir; disposing the halogen reservoir between the first SPC layer and the second SPC layer to produce a layered structure; and The layered structure is attached together to form the article. A method of forming an article comprising:

20. disposing the halogen reservoir between the first SPC layer and the second SPC layer; such that the formed article includes at least one permeation control layer. disposing at least one permeation control layer between the first SPC layer and the halogen reservoir; disposing the at least one permeation control layer between the second SPC layer and the halogen reservoir; or Do both 20. The method of claim 19, comprising:

21. disposing the halogen reservoir between the first SPC layer and the second SPC layer; disposing a first layer of at least one permeation control material between the first SPC layer and the halogen reservoir; and A second layer of at least one permeation control material is disposed between the second SPC layer and the halogen reservoir.

20. The method of claim 19, comprising:

22. 20. The method of claim 19, further comprising combining at least one halogen source with at least one permeation control material to form the halogen reservoir.

23. Combining the at least one halogen source with the at least one permeation control material comprises: heating the at least one permeation control material to a temperature sufficient to melt the at least one permeation control material; and mixing said at least one molten permeation control material with at least one halogen source; 23. The method of claim 22, comprising:

24. 24. The method of claim 23, wherein the temperature sufficient to melt the at least one permeation control material is from 130°C to 180°C.

25. Combining the at least one halogen source with the at least one permeation control material comprises: forming a mixture by dissolving the at least one permeation control material in a solvent; adding at least one halogen source to the mixture of the solvent and the at least one permeation control material; and The solvent is evaporated.

25. The method of any one of claims 22 to 24, comprising:

26. 26. The method of claim 25, further comprising adding particles to the mixture of the at least one halogen source, a solvent, and the at least one permeation control material.

27. 27. The method of claim 26, wherein the particles are carbon particles.

28. Combining the at least one halogen source with the at least one permeation control material comprises: forming a chemical complex having said at least one halogen source and said at least one permeation control material; 23. The method of claim 22, comprising:

29. 29. The method of any one of claims 22 to 28, wherein the at least one halogen source is in solution.

30. 29. The method of any one of claims 22 to 28, wherein the at least one halogen source is in the gas phase.

31. 29. The method of any one of claims 22 to 28, wherein the at least one halogen source is a salt.

32. further comprising flowing a flue gas stream over at least one surface of the article for a period of at least 90 days; the flue gas stream having a temperature of at least 50° C. and a relative humidity of at least 95%; the flue gas stream comprising: At least one SO at a concentration of at least 20 ppm x A compound, at least 1 μg / m based on the total volume of the flue gas stream 3 with a concentration of mercury vapor Including, during flow of the flue gas stream, the release rate of the total halogens in the article does not exceed 0.5% of the total halogens in the article per day; 32. The method of any one of claims 19 to 31.

33. further comprising flowing a flue gas stream over at least one surface of the article for a period of at least 90 days; the flue gas stream having a temperature of at least 20° C. and a relative humidity of at least 95%; the flue gas stream comprising: At least one SO at a concentration of at least 1 ppm x A compound, at least 1 μg / m based on the total volume of the flue gas stream 3 with a concentration of mercury vapor Including, during flow of the flue gas stream, the release rate of the total halogens in the article does not exceed 2% of the total halogens in the article per day; 32. The method of any one of claims 19 to 31.

Citation Information

Patent Citations

  • Method and system for removing mercury in exhaust gas

    JP2004313833A

  • Cylindrical activated carbon filter

    JP2008284473A

  • Mercury adsorbent and method of treating gas using the same

    JP2009226254A

  • Adsorbent and interior skin material for vehicle containing the same

    JP2011092914A

  • Exhaust gas purification system and method using adsorbent polymer composites

    JP2018507776A